Method for manufacturing wiring board
By using a photosensitive material mask as a substrate layer, combined with plasma masking and dry plating, the problem of balancing insulation performance and electrical properties in PCB manufacturing was solved, achieving micro-wiring and simplified processes.
Patent Information
- Application Number
- CN202480021146.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-29
- Filing Date
- 2024-02-15
- Publication Date
- 2025-11-14
AI Technical Summary
Existing wiring board manufacturing methods make it difficult to simultaneously achieve excellent insulation performance and electrical characteristics, as well as fine wiring, when forming through-holes or trenches. Furthermore, mask pattern removal is complex and carries a high risk of damage from chemical solutions.
A photosensitive material-containing mask is used as the base layer. Through-holes or trenches are formed using a plasma mask, and a conductor layer is formed on the plasma mask to avoid mask pattern removal. The conductor layer is formed by combining a dry plating method.
It achieves micro-wiring without the need for mask pattern removal, with excellent insulation and electrical properties, simplifies the process, and reduces the risk of chemical damage.
Smart Images

Figure CN120958575A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing a wiring board and a semiconductor device. Background Technology
[0002] In recent years, there has been a growing demand for thinner designs and finer wiring in wiring boards, such as printed wiring boards, semiconductor packaging substrates, and wafer-level packaging substrates, in order to achieve miniaturization and high functionality in electronic devices. As a method for manufacturing wiring boards, for example, the method described in Patent Document 1 has been proposed.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent document 1: Japanese Patent Application Publication No. 2022-39763. Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] However, in the manufacturing process of wiring boards, vias or trenches are sometimes formed on the insulating layer (sometimes called the "insulating material layer"). As a method for forming vias or trenches on the insulating layer, if the insulating layer is a photosensitive resin, it is done by patterning based on exposure and development; if the insulating layer is a thermosetting resin, it is formed by laser irradiation or plasma treatment or laser irradiation through a mask. Here, "via" generally refers to a hole that penetrates the insulating layer. Conversely, "trench" generally refers to a groove that does not penetrate the insulating layer.
[0008] When the insulating layer is a cured photosensitive material containing a photosensitive resin, it is easy to align the mask pattern by utilizing photolithography, which is beneficial for forming small-diameter vias or small-diameter trenches. However, it is difficult to improve the insulation performance and electrical properties while maintaining the resolution of the photosensitive material.
[0009] On the other hand, when the insulating layer is a cured product of a thermosetting material filled with a large amount of inorganic filler, the insulating layer can improve insulation performance and electrical properties, but the inorganic filler will cause the surface to be uneven, making it difficult to form micro-wires.
[0010] As a solution, an insulating material with a smooth base layer on the surface that is unfilled or contains only a very small amount of inorganic filler has been proposed. However, when opening small-diameter holes, it is difficult to perform high-precision alignment of the pads by laser irradiation. As a result, there is a problem of the increased area occupied by through holes or trenches.
[0011] On the other hand, a release-type photoresist can also be used as a plasma mask to form through-holes and trenches on cured thermosetting materials containing thermosetting resins. However, this requires removing and peeling off the mask pattern, thus increasing the number of steps and making the operation more complex. In addition, during the peeling process, the thermosetting material is exposed to the peeling chemical solution, so there is also the issue of chemical solution damage.
[0012] The objective of this invention is to provide a method for manufacturing a wiring board that eliminates the need for mask pattern removal during the formation of vias or trenches, exhibits excellent insulation and electrical properties of the insulating material layer, and enables micro-wiring; and a semiconductor device.
[0013] means for solving problems
[0014] In order to solve the aforementioned problems, the inventors conducted in-depth research and found that by leaving behind a mask containing photosensitive material used when forming through holes or trenches in thermosetting materials, which remains in the form of a base layer (permanent film), excellent insulation performance and electrical properties are achieved, and micro-wiring can be realized. Thus, the present invention was completed.
[0015] That is, the present invention includes the following contents.
[0016] [1] A method for manufacturing a wiring board, comprising:
[0017] (1) A process of preparing a substrate having a conductor circuit and an insulating material layer formed by a cured thermosetting material on the conductor circuit, and applying or both of photosensitive material coating and pasting to the surface of the insulating material layer to form a photosensitive material layer.
[0018] (2) The process of exposing and developing the photosensitive material layer to form a plasma mask with an opening;
[0019] (3) A process of irradiating an insulating material layer with plasma through a plasma mask, forming either or both of vias and trenches in the insulating material layer at the opening of the plasma mask, and performing a sublimation process on the plasma mask; and
[0020] (4) The process of forming a conductor layer on the surface of a subtractive plasma mask and any one or both of vias and trenches.
[0021] [2] According to the method for manufacturing the wiring board described in [1], step (4) includes:
[0022] (4-1) The process of forming a deposition seed layer on the surface of a subtractive plasma mask and any one or both of vias and trenches; and
[0023] (4-2) The process of plating on the seed layer to form a conductor layer.
[0024] [3] The method of manufacturing a wiring board according to [1] or [2], wherein the conductor layer comprises either or both of conductor wiring formed at a location outside the opening of the plasma mask and conductor aperture layer formed at the opening of the plasma mask.
[0025] [4] According to the method of manufacturing the wiring board described in [2], a plating seed layer is formed by dry plating.
[0026] [5] The method for manufacturing a wiring board according to any one of [1] to [4], wherein the opening diameter of the through hole or trench is 20 μm or less.
[0027] [6] The method for manufacturing a wiring board according to any one of [1] to [5], wherein the thickness of the plasma mask after the reduction film is completed after step (3) is 0.1 μm or more and 20 μm or less.
[0028] [7] The method for manufacturing a wiring board according to any one of [1] to [6], wherein the wiring spacing of the conductor circuit is 0.2 μm or more and 10 μm or less.
[0029] [8] The method for manufacturing a wiring board according to any one of [1] to [7], wherein the arithmetic mean roughness (Ra) of the plasma mask surface after the subtractive film is completed after step (3) is less than 100 nm.
[0030] [9] The method for manufacturing a wiring board according to any one of [1] to [8], wherein the roughness (Sa) of the wall surface of the through hole or trench is 400 nm or less.
[0031]
[10] The method for manufacturing a wiring board according to any one of [1] to [9], wherein the ratio (Ra / Sa) of the arithmetic mean roughness (Ra) of the plasma mask surface after the completion of step (3) to the roughness (Sa) of the wall surface of the via or trench is 3 or less.
[0032]
[11] The method for manufacturing a wiring board according to any one of [1] to
[10] , wherein the thickness of the photosensitive material layer is 1 μm or more and 100 μm or less.
[0033]
[12] In the method for manufacturing a wiring board according to any one of [1] to
[11] , when the thickness of the plasma mask before plasma irradiation is set to 1, the thickness of the plasma mask after the reduction film is 0.7 or less after the completion of step (3).
[0034]
[13] The manufacturing method of the wiring board according to any one of [1] to
[12] , wherein the absolute value of the difference between the linear thermal expansion coefficient of the cured product of the photosensitive material and the linear thermal expansion coefficient of the cured product of the insulating material in the range of 25°C to 150°C is 60 ppm / °C or less.
[0035]
[14] The manufacturing method of the wiring board according to any one of [1] to
[13] , wherein when the thickness of the plasma mask after film reduction at the end of step (2) is set as T1 and the thickness of the insulating material layer at the end of step (2) is set as T2, the relationship of T1 > T2 is satisfied.
[0036]
[15] The manufacturing method of the wiring board according to any one of [1] to
[14] , wherein when the thickness of the plasma mask after film reduction at the end of step (3) is set as T3 and the thickness of the insulating material layer at the end of step (3) is set as T4, the relationship of T3 < T4 is satisfied.
[0037]
[16] The manufacturing method of the wiring board according to any one of [1] to
[15] , wherein the absolute value of the difference between the glass transition temperature of the photosensitive material contained in the plasma mask and the glass transition temperature of the thermosetting material is 100°C or less.
[0038]
[17] The manufacturing method of the wiring board according to any one of [1] to
[16] , wherein the hole taper angle of the through hole or groove is 65 degrees or more and 90 degrees or less.
[0039]
[18] The manufacturing method of the wiring board according to any one of [1] to
[17] , wherein the hole expansion rate is 105% or more and 150% or less.
[0040]
[19] The manufacturing method of the wiring board according to any one of [1] to
[18] , wherein the relative dielectric constant of the cured product of the photosensitive material and the relative dielectric constant of the cured product of the thermosetting material are both 3.5 or less.
[0041]
[20] The manufacturing method of the wiring board according to any one of [1] to
[19] , wherein the elongation at break of the cured product of the photosensitive material is 10% or more, and the elongation at break of the cured product of the photosensitive material is greater than the elongation at break of the cured product of the thermosetting material.
[0042]
[21] The manufacturing method of the wiring board according to any one of [1] to
[20] , wherein the etching rate in step (3) is 100 nm / min or more.
[0043]
[22] The method for manufacturing a wiring board according to any one of [1] to
[21] , wherein the line (width of conductor layer) / spacing (width between conductor layers) (L / S) of the conductor layer is 5 μm / 5 μm or less.
[0044]
[23] The method for manufacturing a wiring board according to any one of [1] to
[22] is a multilayer wiring board substrate comprising three or more conductor layers.
[0045]
[24] The method for manufacturing a wiring board according to any one of [1] to
[23] , wherein the area of the wiring board is 2500 mm². 2 above.
[0046]
[25] The method for manufacturing a wiring board according to any one of [1] to
[24] , wherein the photosensitive material used in step (1) contains at least one selected from resins that can be developed with a developer and epoxy resins.
[0047]
[26] According to the method for manufacturing the wiring board described in
[25] , the resin capable of being developed using a developer contains one or more selected from alkali-soluble resins having phenolic hydroxyl groups within the molecule, polyimide precursors, polybenzoxazole precursor resins, and acrylic resins.
[0048]
[27] The method for manufacturing a wiring board according to any one of [1] to
[26] , wherein the photosensitive material used in step (1) contains an inorganic filler material, and the content of the inorganic filler material in the photosensitive material is 10% by mass or less relative to 100% by mass of the non-volatile components of the photosensitive material.
[0049]
[28] The method for manufacturing a wiring board according to any one of [1] to
[27] , wherein the thermosetting material contains an inorganic filler material, and the content of the inorganic filler material in the thermosetting material is 20% by mass or more relative to 100% by mass of the non-volatile components of the thermosetting material.
[0050]
[29] In the method for manufacturing a wiring board according to
[28] , the content of inorganic filler material is 35% or more and 90% or less of the non-volatile component of the thermosetting material by mass relative to 100% of mass.
[0051]
[30] The method for manufacturing a wiring board according to any one of [1] to
[29] , wherein the photosensitive material used in step (1) contains an inorganic filler material, the average particle size of the inorganic filler material in the photosensitive material is 0.2 μm or less, and the thermosetting material contains an inorganic filler material, the average particle size of the inorganic filler material is 0.01 μm or more.
[0052]
[31] The method for manufacturing a wiring board according to any one of [1] to
[30] , wherein the coefficient of linear thermal expansion of the whole obtained by combining the plasma mask after the reduction film after the completion of step (3) with the insulating material layer is 100 ppm / ℃ or less in the range of 25°C to 150°C.
[0053]
[32] The method for manufacturing a wiring board according to any one of [1] to
[31] , wherein the photosensitive material used in step (1) is a solvent-developable negative photosensitive polyimide resin.
[0054]
[33] The method for manufacturing a wiring board according to any one of [1] to
[32] , wherein step (1) includes at least one of the following: coating a liquid photosensitive material, and pasting a photosensitive material layer comprising a support and a photosensitive material layer formed of the photosensitive material disposed on the support.
[0055]
[34] The method for manufacturing a wiring board according to any one of [1] to
[33] , wherein the total thickness of the insulating material layer and the plasma mask after reduction film is 15 μm or less.
[0056]
[35] The method for manufacturing a wiring board according to any one of [1] to
[34] includes: attaching a thermosetting material layer comprising a support body and a thermosetting material layer formed of a thermosetting material disposed on the support body to a conductor circuit, and curing the thermosetting material layer to form an insulating material layer.
[0057]
[36] A method for manufacturing a wiring board, comprising:
[0058] (A) A process of preparing a substrate having a conductor circuit and an insulating material layer formed on the conductor circuit by a cured thermosetting material, and applying or both of coating and pasting a first photosensitive material to the surface of the insulating material layer to form a first photosensitive material layer.
[0059] (B) The process of exposing and developing the first photosensitive material layer to form a first plasma mask with an opening;
[0060] (C) A process of irradiating an insulating material layer with plasma through a first plasma mask, forming either or both of a via and a trench in the insulating material layer at the opening of the plasma mask, and performing a reduction film process on the plasma mask.
[0061] (D) A process of forming a second photosensitive material layer by coating and pasting a second photosensitive material in a manner that covers the surface and opening of a first plasma mask.
[0062] (E) The process of exposing and developing the second photosensitive material layer to form a second plasma mask with an opening;
[0063] (F) The process of irradiating the first plasma mask and the insulating material layer with plasma through the second plasma mask to form either or both of through holes and trenches in the insulating material layer.
[0064] (G) The process of forming a conductor layer on the surface of the first plasma mask and either or both of the vias and trenches; and
[0065] (H) The process of grinding the surface of the conductor layer.
[0066]
[37] A wiring board manufactured by any one of the wiring board manufacturing methods described in [1] to
[36] .
[0067]
[38] The wiring board according to
[37] is formed in the order of conductor circuit, insulating material layer, plasma mask and conductor layer, and has through holes.
[0068]
[39] The wiring board according to
[38] comprises two or more conductor circuits, an insulating material layer, a plasma mask, a conductor layer and a via.
[0069]
[40] A semiconductor device comprising a wiring board manufactured by any one of the manufacturing methods of wiring boards described in any one of [1] to
[36] .
[0070]
[41] The semiconductor device according to
[40] has a fan-out structure.
[0071]
[42] The semiconductor device according to
[40] has a small chip structure.
[0072]
[43] A semiconductor device having a semiconductor chip on a wiring board manufactured by any one of the manufacturing methods described in [1] to
[36] .
[0073]
[44] The semiconductor device according to any one of
[40] to
[43] , wherein the semiconductor chip is a hybrid system of at least a logic chip and a memory chip.
[0074] Invention Effects
[0075] According to the present invention, a method for manufacturing a wiring board is provided that eliminates the need for mask pattern removal when forming vias or trenches, provides excellent insulation and electrical properties of the insulating material layer, and enables micro-wiring; as well as a semiconductor device. Attached Figure Description
[0076] Figure 1This is a cross-sectional schematic diagram illustrating an example of a substrate in which an insulating material layer is formed on an inner circuit board.
[0077] Figure 2 This is a cross-sectional schematic diagram illustrating an example of a substrate on which an insulating material layer is formed on an inner circuit board, and a photosensitive material layer is formed thereon.
[0078] Figure 3 This is a cross-sectional schematic diagram illustrating an example of a plasma mask being formed in the first embodiment.
[0079] Figure 4 This is a cross-sectional schematic diagram illustrating an example of forming trenches and vias in the insulating material layer and etching the plasma mask in the first embodiment.
[0080] Figure 5 This is a cross-sectional schematic diagram illustrating an example of the situation after trenches and through holes are formed in the insulating material layer in the first embodiment.
[0081] Figure 6 This is a cross-sectional schematic diagram illustrating an example of a case in the first embodiment where a plating seed layer is formed on the surface of a plasma mask and an insulating material layer after a reduction coating.
[0082] Figure 7 This is a cross-sectional schematic diagram illustrating an example of forming a patterned conductor layer on a plated seed layer in the first embodiment.
[0083] Figure 8 This is a cross-sectional schematic diagram illustrating an example of a patterned conductor layer formed in the first embodiment.
[0084] Figure 9 This is a cross-sectional schematic diagram showing another example of a plasma mask being formed in the first embodiment.
[0085] Figure 10 This is a cross-sectional schematic diagram illustrating another example of the case in the first embodiment where trenches and vias are formed in the insulating material layer and the plasma mask is etched.
[0086] Figure 11 This is a cross-sectional schematic diagram showing another example of the situation after trenches and through holes are formed in the insulating material layer in the first embodiment.
[0087] Figure 12 This is a cross-sectional schematic diagram illustrating an example of a case in the first embodiment where a plating seed layer is formed on the surface of a plasma mask and an insulating material layer after a reduction coating.
[0088] Figure 13This is a cross-sectional schematic diagram showing another example of forming a patterned conductor layer on a plated seed layer by plating in the first embodiment.
[0089] Figure 14 This is a cross-sectional schematic diagram showing another example of a patterned conductor layer formed in the first embodiment.
[0090] Figure 15 This is a cross-sectional schematic diagram illustrating an example of a case where a first plasma mask is formed in the second embodiment.
[0091] Figure 16 This is a cross-sectional schematic diagram illustrating an example of forming a trench in the insulating material layer and etching the first plasma mask in the second embodiment.
[0092] Figure 17 This is a cross-sectional schematic diagram illustrating an example of a second embodiment in which a second photosensitive material layer is formed in a manner that covers the surface and openings of the first plasma mask.
[0093] Figure 18 This is a cross-sectional schematic diagram illustrating an example of a second plasma mask being formed in the second embodiment.
[0094] Figure 19 This is a cross-sectional schematic diagram illustrating an example of the situation after a trench is formed in the insulating material layer in the second embodiment.
[0095] Figure 20 This is a cross-sectional schematic diagram illustrating an example of a case where a conductor layer is formed in the second embodiment.
[0096] Figure 21 This is a cross-sectional schematic diagram showing an example of the situation after the surface of the conductor layer has been polished in the second embodiment. Detailed Implementation
[0097] The following describes embodiments and examples in detail with reference to the present invention. However, the present invention is not limited to the embodiments and examples listed below, and can be implemented in any way without departing from the scope of the claims and their equivalents.
[0098] Before providing a detailed description of the manufacturing method of the wiring board of the present invention, the thermosetting material, photosensitive material, thermosetting resin sheet, photosensitive resin sheet, and prepreg used in the manufacturing method of the wiring board of the present invention will be described.
[0099] [Thermosetting materials]
[0100] Thermosetting materials are commonly used to form insulating layers by heat curing, whereby the cured product possesses sufficient hardness and insulation. Examples of such thermosetting materials include compositions comprising thermosetting resins. Thermosetting materials may contain thermosetting resins, and, as needed, further inorganic fillers, curing accelerators, thermoplastic resins, and other additives.
[0101] Thermosetting materials contain thermosetting resins. Existing known thermosetting resins used in forming the insulating layer of a printed wiring board can be used as the thermosetting resin.
[0102] Examples of thermosetting resins include epoxy resins, polyarylene ether resins, free radical polymerizable resins, phenolic resins, naphthol resins, benzoxazine resins, reactive ester resins, cyanate ester resins, carbodiimide resins, amine resins, and acid anhydride resins. A single thermosetting resin can be used alone, or two or more resins can be used in any ratio. Hereinafter, resins such as phenolic resins, naphthol resins, benzoxazine resins, reactive ester resins, cyanate ester resins, carbodiimide resins, amine resins, and acid anhydride resins, which can react with epoxy resins to cure thermosetting materials, are sometimes collectively referred to as "curing agents." From the viewpoint of forming an insulating layer, the thermosetting resin preferably includes an epoxy resin and a curing agent, and more preferably includes any one of epoxy resins, reactive ester resins, phenolic resins, and cyanate ester resins. One epoxy resin and one curing agent can be used alone, or two or more resins can be used in combination.
[0103] Epoxy resins, as thermosetting resins, include, for example, bixylenol-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol S-type epoxy resins, bisphenol AF-type epoxy resins, dicyclopentadiene-type epoxy resins, triphenol-type epoxy resins, naphthol phenolic varnish-type epoxy resins, phenol phenolic varnish-type epoxy resins, tert-butyl-catechol-type epoxy resins, naphthalene-type epoxy resins, naphthol-type epoxy resins, anthracene-type epoxy resins, glycidylamine-type epoxy resins, glycidyl ester-type epoxy resins, cresol phenolic varnish-type epoxy resins, biphenyl-type epoxy resins, linear aliphatic epoxy resins, epoxy resins with butadiene structures, alicyclic epoxy resins, heterocyclic epoxy resins, epoxy resins containing spirocyclic rings, cyclohexane-type epoxy resins, cyclohexanediethanol-type epoxy resins, naphthyl ether-type epoxy resins, tris(hydroxymethyl)-type epoxy resins, and tetraphenylethane-type epoxy resins.
[0104] In thermosetting materials, epoxy resins having two or more epoxy groups per molecule are preferred as thermosetting resins. From the viewpoint of significantly obtaining the desired effects of the present invention, the proportion of epoxy resin having two or more epoxy groups per molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more, relative to 100% by mass of the non-volatile components of the epoxy resin.
[0105] Epoxy resins exist in two states: liquid epoxy resin at 20°C (hereinafter sometimes referred to as "liquid epoxy resin") and solid epoxy resin at 20°C (hereinafter sometimes referred to as "solid epoxy resin"). In thermosetting materials, the thermosetting resin may comprise only liquid epoxy resin or only solid epoxy resin. From the viewpoint of significantly obtaining the effects of the present invention, a combination comprising both liquid and solid epoxy resin is preferred.
[0106] As a liquid epoxy resin, it is preferred to be a liquid epoxy resin having two or more epoxy groups in one molecule.
[0107] As liquid epoxy resins, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidylamine type epoxy resin, phenolic varnish type epoxy resin, alicyclic epoxy resin with ester skeleton, cyclohexane type epoxy resin, cyclohexanediol type epoxy resin, glycidylamine type epoxy resin and epoxy resin with butadiene structure are preferred, and bisphenol A type epoxy resin and bisphenol F type epoxy resin are more preferred.
[0108] Specific examples of liquid epoxy resins include: DIC's "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resin); Mitsubishi Chemical's "828US", "jER828EL", "825", and "EPIKOTE828EL" (bisphenol A type epoxy resin); Mitsubishi Chemical's "jER807" and "1750" (bisphenol F type epoxy resin); Mitsubishi Chemical's "jER152" (phenolic varnish type epoxy resin); Mitsubishi Chemical's "630" and "630LSD" (glycidylamine type epoxy resin); Nippon Steel Chemical & Materials Co., Ltd.'s "ZX1059" (a mixture of bisphenol A and bisphenol F type epoxy resins); Nagase ChemteX's "EX-721" (glycidyl ester type epoxy resin); and DAICL's "CELLOXIDE". 2021P (alicyclic epoxy resin with an ester backbone); PB-3600 (butadiene-structured epoxy resin) manufactured by DAIICEL; ZX1658 and ZX1658GS (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by JITAC Chemicals & Materials Co., Ltd., etc. They can be used alone or in combination of two or more.
[0109] As a solid epoxy resin, it is preferred to be a solid epoxy resin having three or more epoxy groups in one molecule, and more preferably an aromatic solid epoxy resin having three or more epoxy groups in one molecule.
[0110] As a solid epoxy resin, the preferred types are xylenol-type epoxy resin, naphthalene-type epoxy resin, naphthalene-type tetrafunctional epoxy resin, cresol-phenolic varnish-type epoxy resin, dicyclopentadiene-type epoxy resin, triphenol-type epoxy resin, naphthol-type epoxy resin, biphenyl-type epoxy resin, naphthalene ether-type epoxy resin, anthracene-type epoxy resin, bisphenol A-type epoxy resin, bisphenol AF-type epoxy resin, and tetraphenylethane-type epoxy resin, with naphthalene-type epoxy resin being more preferred.
[0111] As a solid epoxy resin, the preferred types are naphthalene-type tetrafunctional epoxy resin, cresol-phenolic varnish-type epoxy resin, dicyclopentadiene-type epoxy resin, triphenol-type epoxy resin, naphthol-type epoxy resin, biphenyl-type epoxy resin, naphthalene ether-type epoxy resin, anthracene-type epoxy resin, bisphenol A-type epoxy resin, and tetraphenylethane-type epoxy resin, with naphthalene-type tetrafunctional epoxy resin, naphthol-type epoxy resin, and biphenyl-type epoxy resin being more preferred. Specific examples of solid epoxy resins include: DIC's "HP4032H" (naphthalene-type epoxy resin), "HP-4700", "HP-4710" (naphthalene-type tetrafunctional epoxy resin), "N-690" (cresol phenolic varnish type epoxy resin), "N-695" (cresol phenolic varnish type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", and "HP6000" (naphthalene ether type epoxy resin); and Nippon Kayaku Co., Ltd.'s "EPPN-502H" (triphenol type epoxy resin), "NC7000L" (naphthalene phenolic varnish type epoxy resin), and "NC3" (…). 000H, NC3000, NC3000L, NC3100 (biphenyl type epoxy resin); Nippon Steel Chemical & Materials Co., Ltd.'s "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthalene phenolic varnish type epoxy resin); Mitsubishi Chemical Co., Ltd.'s "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bi-xylenol type epoxy resin), and "YX8800" (anthracite type epoxy resin); Osaka Gas Chemical Co., Ltd.'s "PG-100" and "CG-500"; Mitsubishi Chemical Co., Ltd.'s "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), and "jER1031S" (tetraphenylethane type epoxy resin), etc. They can be used individually or in combination of two or more.
[0112] When liquid epoxy resin and solid epoxy resin are used in combination as thermosetting resins, their mass ratio (liquid epoxy resin: solid epoxy resin) is preferably 1:0.1 to 1:20, more preferably 1:0.3 to 1:18, and particularly preferably 1:0.5 to 1:15. By keeping the mass ratio of liquid epoxy resin to solid epoxy resin within this range, the desired effects of the present invention can be significantly obtained. Furthermore, when used typically in the form of thermosetting resin sheets, moderate adhesiveness is achieved. In addition, when used typically in the form of thermosetting resin sheets, sufficient flexibility is obtained, and processability is improved. Furthermore, a cured product with sufficient tensile strength can generally be obtained.
[0113] The epoxy equivalent of the epoxy resin used as a thermosetting resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. By falling within this range, a cured product with sufficient crosslinking density of the thermosetting material can be achieved. The epoxy equivalent is the mass of epoxy resin containing 1 equivalent of epoxy groups. This epoxy equivalent can be determined according to JIS K7236.
[0114] From the viewpoint of significantly achieving the desired effects of the present invention, the weight-average molecular weight (Mw) of the epoxy resin as a thermosetting resin is preferably 100 to 5000, more preferably 250 to 3000, and even more preferably 400 to 1500. The weight-average molecular weight of the epoxy resin is the weight-average molecular weight converted from polystyrene by gel permeation chromatography (GPC).
[0115] From the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability, when the non-volatile component in the thermosetting material is set to 100% by mass, the content of epoxy resin as the thermosetting resin is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. From the viewpoint of significantly obtaining the desired effects of the present invention, the upper limit of the epoxy resin content is preferably 60% by mass or less, more preferably 55% by mass or less, and particularly preferably 50% by mass or less.
[0116] Unless otherwise specified, the content of each component in a thermosetting material is the value when the non-volatile component in the thermosetting material is set to 100% by mass. The non-volatile component refers to the total non-volatile component in the thermosetting material excluding solvents.
[0117] Regarding the content of epoxy resin as a thermosetting resin, from the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the thermosetting material is set to 100% by mass, it is preferably 10% by mass or more, more preferably 15% by mass or more, further preferably 20% by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less. Resin component refers to the non-volatile components in the thermosetting material, excluding inorganic fillers.
[0118] As thermosetting resins, polyarylether resins are not particularly limited in type as long as they possess a polyarylether backbone and exhibit crosslinking properties through the reaction of terminal hydroxyl groups and other functional groups. Examples of polyarylether resins include polyphenylene ether resins and polynaphthalene ether resins, which can be homopolymers or copolymers. Examples of homopolymers of polyphenylene ether resins include those containing 2,6-dicarbonyl groups.1~3 Homopolymers of alkyl-1,4-phenyl ether units, as copolymers thereof, include, for example, those in 2,6-dicarbonyl groups. 1~3 The alkyl-1,4-phenyl ether unit contains 2,3,6-tricarbonyl groups. 1~3 Grafted, block, or random copolymers of alkyl-1,4-phenyl ether units, etc. Examples of polyaryl ether resins include, for example, "Noryl (registered trademark) SA90" manufactured by SABIC.
[0119] The number-average molecular weight (Mn) of the polyarylene ether resin is preferably 200–5,000, more preferably 400–3,000, and even more preferably 600–2,500. The Mn of the polyarylene ether resin can be determined by GPC in the form of a polystyrene equivalent.
[0120] The type of free-radical polymerizable resin as a thermosetting resin is not particularly limited as long as it has one or more (preferably two or more) free-radical polymerizable unsaturated groups in one molecule. Examples of free-radical polymerizable resins include resins having one or more free-radical polymerizable unsaturated groups selected from maleimide, vinyl, allyl, styrene, vinylphenyl, acryloyl, methacryloyl, fumaroyl, and maleyl. From the viewpoint of achieving a cured product that simultaneously exhibits good insulation and good heat resistance, the free-radical polymerizable resin preferably contains one or more selected from maleimide resins, (meth)acrylic resins, and styrene resins.
[0121] As a maleimide resin, there is no particular limitation on its type as long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrole-1-yl) in one molecule. Examples of maleimide resins include, for instance, "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all from Designer Molecules Inc.), which contain an aliphatic backbone (preferably an aliphatic backbone containing a ring structure with 10 or more carbon atoms, more preferably an aliphatic backbone with 36 carbon atoms derived from a dimer diamine); the maleimide resin containing an indane backbone described in Patent Application Publication No. 2020-500211; and maleimide resins containing an aromatic ring backbone directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000", "BMI-1000" (manufactured by Yamato Kasei Co., Ltd.), and "BMI-80" (manufactured by KI Kasei Co., Ltd.).
[0122] As a (meth)acrylic resin, there is no particular limitation on its type as long as it has one or more (meth)acryloyl groups in one molecule, and it can be a monomer or an oligomer. Here, the term "(meth)acryloyl group" is a general term for acryloyl group and methacryloyl group. In addition to (meth)acrylate monomers, other examples of (meth)acrylic resins include "A-DOG" (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), "DCP-A" (manufactured by Kyoesha Chemical Co., Ltd.), "NPDGA", "FM-400", "R-687", "THE-330", "PET-30", and "DPHA" (all manufactured by Nippon Kayaku Co., Ltd.).
[0123] As a styrene-based resin, there is no particular limitation on its type, as long as it has one or more (preferably two or more) styrene or vinylphenyl groups in one molecule; it can be a monomer or an oligomer. Examples of styrene-based resins include "OPE-2St", "OPE-2St 1200", and "OPE-2St 2200" (all manufactured by Mitsubishi Gas Chemical Co., Ltd.). In addition to styrene monomers, examples of styrene-based resins include homopolymers of aromatic divinyl compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl) ether, or copolymers of these aromatic divinyl compounds with aromatic monovinyl compounds such as styrene, vinyltoluene, ethylstyrene, and vinylnaphthalene.
[0124] Regarding the reactive ester resin as a thermosetting resin, a resin having one or more reactive ester groups per molecule can be used. Among these, resins having two or more highly reactive ester groups per molecule, such as phenolic esters, thiophenolic esters, N-hydroxyamine esters, and heterocyclic hydroxyl compounds, are preferred as reactive ester resins. This reactive ester resin is preferably obtained through a condensation reaction of a carboxylic acid compound and / or a thiocarboxylic acid compound with a hydroxyl compound and / or a thiol compound. Especially from the viewpoint of improving heat resistance, reactive ester resins obtained from carboxylic acid compounds and hydroxyl compounds are preferred, and reactive ester resins obtained from carboxylic acid compounds and phenolic compounds and / or naphthol compounds are more preferred.
[0125] Examples of carboxylic acid compounds include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.
[0126] Examples of phenolic or naphthol compounds include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthol, 1,6-dihydroxynaphthol, 2,6-dihydroxynaphthol, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyroglucinol, dicyclopentadiene-type diphenol compounds, and phenolic varnishes. Here, "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0127] Preferred examples of reactive ester resins include reactive ester resins containing a dicyclopentadiene-type diphenol structure, reactive ester resins containing a naphthalene structure, reactive ester resins containing an acetylated form of phenolic varnish, and reactive ester resins containing a benzoylated form of phenolic varnish. More preferably, reactive ester resins containing a naphthalene structure and reactive ester resins containing a dicyclopentadiene-type diphenol structure are preferred. "Dicyclopentadiene-type diphenol structure" refers to a divalent structural unit containing a phenylene-dicyclopentylene-phenylene group.
[0128] Commercially available reactive ester resins include, for example, "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation) as reactive ester resins containing a dicyclopentadiene-type diphenol structure; and for example, "EXB9416-70BK", "EXB-8100L-65T", "EXB-8150L-65T", "EXB-8150-65T", "HPC-8150-60T", "HPC-8150-62T" (manufactured by DIC Corporation) and "PC1300-02-6". 5T (manufactured by AIRWATER); as an active ester resin containing acetylated phenolic varnishes, examples include "DC808" (manufactured by Mitsubishi Chemical); as an active ester resin containing benzoylation of phenolic varnishes, examples include "YLH1026" (manufactured by Mitsubishi Chemical); as an active ester resin belonging to acetylated phenolic varnishes, examples include "DC808" (manufactured by Mitsubishi Chemical); as an active ester resin belonging to benzoylation of phenolic varnishes, examples include "YLH1026" (manufactured by Mitsubishi Chemical), "YLH1030" (manufactured by Mitsubishi Chemical), "YLH1048" (manufactured by Mitsubishi Chemical); "EXB-8500-65T" (manufactured by DIC), etc.
[0129] From the viewpoint of achieving significant effects of the present invention, the content of the active ester resin as the thermosetting resin is preferably 1% or more by mass relative to 100% by mass of the non-volatile components in the thermosetting material, more preferably 2% or more by mass, further preferably 3% or more by mass, preferably 30% or less by mass, more preferably 25% or less by mass, and further preferably 20% or less by mass.
[0130] From the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the thermosetting material is set to 100% by mass, the content of the active ester resin as the thermosetting resin is preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 5% by mass or more, preferably 50% by mass or less, more preferably 45% by mass or less, and further preferably 40% by mass or less.
[0131] Regarding phenolic and naphthol-based resins as thermosetting resins, from the viewpoint of heat resistance and water resistance, a phenolic varnish structure is preferred. Furthermore, from the viewpoint of adhesion to the conductor layer, a nitrogen-containing phenolic resin is preferred, and a phenolic resin containing a triazine backbone is more preferred.
[0132] Specific examples of phenolic and naphthol resins include: "MEH-7700", "MEH-7810", "MEH-7851" manufactured by Meiwa Kasei Corporation; "NHN", "CBN", "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", "SN395" manufactured by Nippon Steel Chemicals & Materials Co., Ltd.; and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", "EXB-9500" manufactured by DIC Corporation.
[0133] From the viewpoint of achieving significant effects of the present invention, the content of phenolic resin or naphthol resin as thermosetting resin is preferably 1% or more by mass relative to 100% by mass of non-volatile components in the thermosetting material, more preferably 1.5% or more by mass, further preferably 2% or more by mass, preferably 20% or less by mass, more preferably 15% or less by mass, and further preferably 10% or less by mass.
[0134] From the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the thermosetting material is set to 100% by mass, the content of phenolic resin or naphthol resin as the thermosetting resin is preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 3% by mass or more, preferably 40% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less.
[0135] Regarding cyanate ester resins as thermosetting resins, examples include difunctional cyanate ester resins such as bisphenol A dicyanate, polyphenol cyanate, oligomeric (3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethoxydiphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate-phenyl)propane, 1,1-bis(4-cyanate-phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate-phenyl-1-(methylethoxy))benzene, bis(4-cyanate-phenyl) sulfide, and bis(4-cyanate-phenyl) ether; polyfunctional cyanate ester resins derived from phenolic varnishes and cresol varnishes; and prepolymers formed by partially triazinizing these cyanate ester resins. Specific examples of cyanate ester resins include Arxada's "PT30", "PT30S" and "PT60" (phenolic varnish type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers formed by triazinization of part or all of bisphenol A dicyanate to form trimers), etc.
[0136] From the viewpoint of achieving significant effects of the present invention, the content of the cyanate ester resin as the thermosetting resin is preferably 1% or more by mass relative to 100% by mass of the non-volatile components in the thermosetting material, more preferably 2% or more by mass, further preferably 3% or more by mass, preferably 25% or less by mass, more preferably 20% or less by mass, and further preferably 15% or less by mass.
[0137] From the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the thermosetting material is set to 100% by mass, the content of the cyanate ester resin as the thermosetting resin is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less.
[0138] Examples of benzoxazine resins, carbodiimide resins, and acid anhydride resins as thermosetting resins can be cited from the resins described in Japanese Patent Application Publication No. 2020-75977.
[0139] When the thermosetting resin contains epoxy resin and a curing agent, the ratio of epoxy resin to all curing agent is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.05 to 1:3, and even more preferably 1:0.1 to 1:2, based on the ratio of [total number of epoxy groups in the epoxy resin] to [total number of active groups in the curing agent]. Here, "total number of epoxy groups in the epoxy resin" refers to the sum of all values obtained by dividing the mass of the non-volatile component of the epoxy resin present in the thermosetting material by the epoxy equivalent. Similarly, "total number of active groups in the curing agent" refers to the sum of all values obtained by dividing the mass of the non-volatile component of the curing agent present in the thermosetting material by the active group equivalent. By keeping the ratio of epoxy resin to curing agent within this range, a cured product with excellent flexibility can be obtained.
[0140] From the viewpoint of achieving significant effects of the present invention, the content of the curing agent as the thermosetting resin is preferably 1% or more by mass relative to 100% by mass of the non-volatile components in the thermosetting material, more preferably 3% or more by mass, further preferably 5% or more by mass, preferably 40% or less by mass, more preferably 35% or less by mass, and further preferably 30% or less by mass.
[0141] From the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the thermosetting material is set to 100% by mass, the content of the curing agent as the thermosetting resin is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, preferably 60% by mass or less, more preferably 55% by mass or less, and further preferably 50% by mass or less.
[0142] From the viewpoint of achieving significant effects of the present invention, the content of thermosetting resin relative to 100% by mass of non-volatile components in the thermosetting material is preferably 6% by mass or more, more preferably 13% by mass or more, even more preferably 20% by mass or more, preferably 65% by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less.
[0143] From the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the thermosetting material is set to 100% by mass, the content of the thermosetting resin is preferably 15% by mass or more, more preferably 23% by mass or more, even more preferably 30% by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 80% by mass or less.
[0144] Thermosetting materials preferably contain inorganic fillers. By incorporating inorganic fillers into the thermosetting resin, the electrical properties of the insulating layer can be improved. One type of inorganic filler can be used alone, or two or more can be used in combination.
[0145] Inorganic compounds can be used as inorganic filler materials. Examples of inorganic filler materials include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica and alumina are suitable, with silica being particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Furthermore, spherical silica is preferred as silica.
[0146] Commercially available inorganic filler materials include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemicals & Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by ADMATECHS Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by DENKA Co., Ltd.; "SILFIL NSS-3N", "SILFIL NSS-4N", and "SILFIL NSS-5N" manufactured by TOKUYAMA Co., Ltd.; "Selphys" and "MGH-005" manufactured by Pacific Cement Co., Ltd.; and "Esferacle" and "BA-1" manufactured by Nippon Chemicals Co., Ltd.
[0147] The preferred specific surface area for inorganic filler materials is 1 m². 2 / g or more, preferably 2m 2 / g or more, preferably 3m 2 / g or more. There is no specific upper limit, but 60mg is preferred. 2 / g or less, 50m 2 / g or less or 40m 2 / g or less. Specific surface area can be determined using a fully automated BET specific surface area measuring device (Macsorb HM-1210 manufactured by MOUNTECH), which adsorbs nitrogen gas onto the sample surface and uses the BET multi-point method.
[0148] The average particle size of the inorganic filler material is preferably 0.01 μm or more, more preferably 0.03 μm or more, particularly preferably 0.05 μm or more, preferably 5 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less.
[0149] The average particle size of inorganic fillers can be determined using laser diffraction / scattering based on the Mie scattering theory. Specifically, a laser diffraction-scattering particle size distribution measuring device can be used to create a volume-based particle size distribution of the inorganic filler, and the median particle size can be used as the average particle size for measurement. The sample can be prepared by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing them ultrasonically for 10 minutes. For the sample, a laser diffraction-scattering particle size distribution measuring device can be used, with the light source wavelength set to blue and red, to measure the volume-based particle size distribution of the inorganic filler using a flow cell method. The average particle size is then calculated from the obtained particle size distribution as the median particle size. Examples of laser diffraction-scattering particle size distribution measuring devices include the "LA-960" manufactured by Horiba Manufacturing Co., Ltd.
[0150] From the perspective of improving moisture resistance and dispersibility, inorganic filler materials are preferably treated with surface treatment agents. Examples of surface treatment agents include vinyl silane coupling agents, (meth)acrylic acid coupling agents, fluorinated silane coupling agents, amino silane coupling agents, epoxy silane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, and titanate coupling agents. A single surface treatment agent can be used, or two or more can be used in combination.
[0151] Commercially available surface treatment agents include, for example, Shin-Etsu Chemical Industry Co., Ltd.'s "KBM1003" (vinyltriethoxysilane), "KBM503" (3-methacryloyloxypropyltriethoxysilane), "KBM403" (3-epoxypropoxypropyltrimethoxysilane), "KBM803" (3-mercaptopropyltrimethoxysilane), and "KBE903" (3-aminopropyltrimethoxysilane). Products such as N-phenyl-3-aminopropyltriethoxysilane, KBM573 (N-phenyl-3-aminopropyltrimethoxysilane), SZ-31 (hexamethyldisilazane), KBM103 (phenyltrimethoxysilane), KBM-4803 (long-chain epoxy silane coupling agent), and KBM-7103 (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0152] From the viewpoint of improving the dispersibility of inorganic filler materials, the degree of surface treatment based on the surface treatment agent is preferably within a specified range. Specifically, 100 parts by mass of inorganic filler material is preferably surface treated with 0.2 parts by mass to 5 parts by mass of surface treatment agent, preferably with 0.2 parts by mass to 3 parts by mass, and preferably with 0.3 parts by mass to 2 parts by mass.
[0153] The degree of surface treatment by the surface treatment agent can be evaluated based on the carbon content per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of the inorganic filler is preferably 0.02 mg / m². 2 The above, more preferably 0.1 mg / m 2 The above is further preferred to be 0.2 mg / m³. 2 That's all. On the other hand, from the viewpoint of suppressing the increase in melt viscosity of the resin varnish and melt viscosity in flake form, 1 mg / m³ is preferred. 2 The following is more preferably 0.8 mg / m³ 2 The following is a further preferred value: 0.5 mg / m³ 2 the following.
[0154] The carbon content per unit surface area of inorganic filler materials can be determined after cleaning the surface-treated inorganic filler material with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the surface-treated inorganic filler material, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid components, the carbon content per unit surface area of the inorganic filler material can be determined using a carbon analyzer. A suitable carbon analyzer is the "EMIA-320V" manufactured by Horiba Seisakusho Co., Ltd.
[0155] The content of inorganic filler material relative to 100% by mass of non-volatile components in thermosetting material is preferably 20% by mass or more, more preferably 30% by mass or more, further preferably 25% by mass or more, further preferably 30% by mass or more, further preferably 35% by mass or more, particularly preferably 40% by mass or more, preferably 90% by mass or less, more preferably 87% by mass or less, and further preferably 83% by mass or less.
[0156] Thermosetting materials may include curing accelerators as needed. Examples of curing accelerators include phosphorus-based, amine-based, imidazole-based, guanidine-based, and metal-based curing accelerators. Among these, amine-based curing accelerators are preferred. A single curing accelerator may be used alone, or two or more may be used in combination.
[0157] Examples of amine-based curing accelerators include trialkylamines such as triethylamine and tributylamine; 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)undecene being preferred.
[0158] Other examples of curing accelerators include substances described in Japanese Patent Application Publication No. 2020-75977.
[0159] The content of the curing accelerator relative to 100% by mass of the non-volatile components in the thermosetting material is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, even more preferably 0.01% by mass or more, preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.3% by mass or less.
[0160] The content of the curing accelerator relative to 100% by mass of the resin component in the thermosetting material is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.1% by mass or more, preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and even more preferably 1.0% by mass or less.
[0161] Thermosetting materials may include thermoplastic resins as needed. Examples of thermoplastic resins include phenoxy resins, polyvinyl acetal resins, polyolefin resins, polyimide resins, polyamide-imide resins, polyether-imide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polyetheretherketone resins, and polyester resins, with phenoxy resins being preferred. A single thermoplastic resin may be used alone, or two or more may be used in combination.
[0162] The weight-average molecular weight of the thermoplastic resin, converted from polystyrene, is preferably 8,000 or more, more preferably 10,000 or more, and even more preferably 20,000 or more. The upper limit is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, and particularly preferably 50,000 or less.
[0163] Examples of phenoxy resins include those having one or more skeletons selected from the following: bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, phenolic varnish skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal group of the phenoxy resin can be any functional group such as a phenolic hydroxyl group or an epoxy group. A single phenoxy resin can be used alone, or two or more can be used in combination. Specific examples of phenoxy resins include Mitsubishi Chemical's "1256" and "4250" (both phenoxy resins containing a bisphenol A backbone), "YX8100" (a phenoxy resin containing a bisphenol S backbone), and "YX6954" (a phenoxy resin containing a bisphenol acetophenone backbone). Other examples include Nippon Steel Chemical & Materials Co., Ltd.'s "FX280" and "FX293," and Mitsubishi Chemical's "YL7500BH30," "YX6954BH30," "YX7553," "YX7553BH30," "YL7769BH30," "YL6794," "YL7213," "YL7290," and "YL7482," etc.
[0164] Other examples of thermoplastic resins include substances described in Japanese Patent Application Publication No. 2020-75977.
[0165] When the non-volatile component in the thermosetting material is set to 100% by mass, the content of the thermoplastic resin is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more. The upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0166] When the resin content in the thermosetting material is set to 100% by mass, the content of thermoplastic resin is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more. The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0167] In addition to the components mentioned above, thermosetting materials may also contain other additives. Examples of such additives include polymerization initiators, organometallic compounds, colorants, polymerization inhibitors, leveling agents, thickeners, defoamers, UV absorbers, adhesion modifiers, bonding agents, antioxidants, fluorescent whitening agents, surfactants, flame retardants, dispersants, stabilizers, photopolymerization initiators, and photosensitizers. Other additives may be used individually or in combination of two or more.
[0168] Thermosetting materials may contain solvents as volatile components. Examples of solvents include ketones such as methyl ethyl ketone (MEK) and cyclohexanone; aromatic hydrocarbons such as xylene and tetramethylbenzene; glycol ethers such as methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, butyl cellosolve acetate, carbitol acetate, and ethyl diethylene glycol acetate; aliphatic hydrocarbons such as octane and decane; petroleum-based solvents such as petroleum ether, naphtha, hydrogenated naphtha, and solvent naphtha; and ether ester solvents such as propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diethylene glycol acetate, γ-butyrolactone, and methyl methoxypropionate. These solvents can be used individually or in combination of two or more.
[0169] Thermosetting materials may contain solvents, preferably in small amounts. The amount of solvent contained in the thermosetting material is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less, relative to 100% by mass of the non-volatile components in the thermosetting material.
[0170] There are no particular limitations on the preparation method of thermosetting materials. Examples include methods that use a mixing or stirring device to mix / disperse the compounding components with a solvent as required.
[0171] Cured thermosetting materials typically exhibit a high glass transition temperature (Tg). Therefore, when an insulating material layer is formed from this cured material, an insulating material layer with a high glass transition temperature can be obtained. The glass transition temperature of the cured material is preferably 130°C or higher, more preferably 140°C or higher, and even more preferably 150°C or higher. There is no particular upper limit; for example, it can be set to 400°C or lower. The glass transition temperature can be measured using the method described in the examples below.
[0172] Cured thermosetting materials typically exhibit a low coefficient of linear thermal expansion (CTE). Therefore, when an insulating material layer is formed from this cured material, an insulating material layer with a low CTE can be obtained. The CTE of the cured material is preferably 100 ppm / °C or less, more preferably 80 ppm / °C or less, and even more preferably 75 ppm / °C or less. The lower limit is not particularly limited, and for example, it can be set to 0.01 ppm / °C or more. The CTE can be measured using the method described in the examples below.
[0173] Cured thermosetting materials typically exhibit a high modulus of elasticity at 23°C. Therefore, an insulating material layer with excellent crack resistance can be obtained. The modulus of elasticity of the cured material at 23°C is preferably 1.0 GPa or higher, more preferably 1.5 GPa or higher, and even more preferably 2.0 GPa or higher. There is no particular upper limit, and it can be set to 50 GPa or lower, etc. The modulus of elasticity can be measured using the method described in the examples below.
[0174] Cured thermosetting materials typically exhibit high elongation (elongation at break). Therefore, insulating material layers with high elongation at break can be obtained. The elongation at break of the cured material is preferably 0.5% or more, more preferably 1.0% or more, and particularly preferably 1.5% or more. There is no particular upper limit; for example, it can be 10% or less. The elongation can be measured according to the method described in the examples below.
[0175] Cured thermosetting materials typically exhibit a low dielectric loss tangent. Therefore, it is possible to obtain an insulating material layer with a low dielectric loss tangent. The dielectric loss tangent of the cured material is preferably 0.03 or less, more preferably 0.02 or less, and even more preferably 0.01 or less. The lower limit of the dielectric loss tangent is not particularly limited, and for example, it can be 0.0005 or more. The dielectric loss tangent can be measured using the method described in the examples below.
[0176] Cured thermosetting materials typically exhibit a low relative permittivity. Therefore, insulating material layers with low relative permittivity can be obtained. The permittivity of the cured material is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.5 or less. The lower limit is not particularly limited; for example, it can be set to 0.0001 or more. The relative permittivity can be measured using the method described in the examples below.
[0177] [Photosensitive materials]
[0178] The photosensitive material only needs to be suitable for forming a plasma mask and have excellent clarity. The photosensitive material can be either a positive or negative photosensitive material. Examples of such photosensitive materials include compositions containing resins that can be developed using a developing solution such as an alkaline aqueous solution. The photosensitive material contains a resin that can be developed using a developing solution, and may further include, as needed, epoxy resin, crosslinking agent, photopolymerization initiator, photoacid generator, bonding agent, organic filler, and other additives.
[0179] The photosensitive material contains a resin that can be developed using a developer. As the resin that can be developed using a developer, conventionally known resins used in forming the solder resist layer of a printed wiring board can be used. Examples of resins that can be developed using a developer include alkali-soluble resins having intramolecular phenolic hydroxyl groups, polybenzoxazole precursor resins, polyimide precursors, p-hydroxystyrene / styrene copolymers, acrylic resins, and methacrylic resins. Preferably, the resin that can be developed using a developer contains one or more selected from alkali-soluble resins having intramolecular phenolic hydroxyl groups, polyimide precursors, polybenzoxazole precursor resins, and acrylic resins. One type of resin that can be developed using a developer can be used alone, or two or more types can be used in combination.
[0180] Examples of alkali-soluble resins containing phenolic hydroxyl groups within their molecules include: Asahi Organic Materials Co., Ltd.'s "TR4020G"; Asahi Organic Materials Co., Ltd.'s "TR4050G", "TR4080G", "TR5020G", "TR5050G", "TR6020G", "TR6050G", and "TR6080G" AV Light series; Sumitomo Bakelite Co., Ltd.'s photoresist resin series; Gunei Chemical Industry Co., Ltd.'s RESITOP series; DIC Co., Ltd.'s "PR-30-40P", "PR-100L", "PR-100H", "PR-50", "PR-55", "PR-56-1", "PR-56-2", "WR-101", "WR-102", "WR-103", and "WR-104" phenolite series; and Reginay Co., Ltd.'s "LF-100". "LF-110", "LF-120", "LF-200", "LF-400", "LF-500"; Meiwa Chemical Co., Ltd.'s series of matrix resins for photoresists; Meiwa Chemical Co., Ltd.'s "MEHC-7851SS", "MEHC-78004S", "MEHC-7851-SS", "MEHC-7851-S", "MEHC-7851-M", "MEHC-7851-H", "MEHC-7800-4S", "MEHC-7800-SS" MEHC-7800-S, MEHC-7800-M, MEHC-7800-H; GPH-65, GPH-103, and MEHC-7841-4S manufactured by Nippon Kayaku Co., Ltd.; BisE and BisP-TMC manufactured by Honshu Chemical Co., Ltd.; and BisA, BisF, BisP-M, BisP-AP, BisP-MIBK, BisP-B, and BisF manufactured by Mitsui Chemicals Fine Chemicals Co., Ltd. s-Z", "BisP-CP", "o,o'-BPF", "BisP-IOTD", "BisP-IBTD", "BisP-DED", "BisP-BA", "Bis-C", "Bis26X-A", "BisO PP-A", "BisOTBP-A", "BisOCHP-A", "BisOFP-A", "BisOC-Z", "BisOC-FL", "BisOC-CP", "BisOCHP-Z", "methylene bis P-CR (メチレンビスP-CR)", "TM-BPF", "BisOC-F", "Bis3M6B-IBTD", "BisOC-IST", "BisP-IST", "BisP-PRM", "BisP-LV", etc.
[0181] Examples of polybenzoxazole precursor resins, polyimide precursors, p-hydroxystyrene / styrene copolymers, and acrylic resins include substances described in Japanese Patent Application Publication No. 2018-169547, Japanese Patent Application Publication No. 2018-169627, International Publication No. 2010 / 134207, International Publication No. 2014 / 069202, Japanese Patent Application Publication No. 2020-101813, and International Publication No. 2018 / 232214.
[0182] Other examples of resins capable of development using a developer include free radical polymerizable resins. Specific examples include acrylic resins, methacrylic resins, and other resins possessing free radical polymerizable unsaturated groups such as olefinic unsaturated groups. Examples of resins possessing free radical polymerizable unsaturated groups include substances described in documents such as Japanese Patent Application Publication No. 2020-15859, Japanese Patent Application Publication No. 2020-52288, and Japanese Patent Application Publication No. 2018-169547.
[0183] The weight-average molecular weight of the resin capable of being developed using the developer is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more, and can be 300 or more, 500 or more, 700 or more, 1000 or more, etc. Furthermore, the upper limit is preferably 150,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less, and can be 10,000 or less, 5,000 or less, 1,000 or less, 800 or less, 500 or less, etc.
[0184] When the non-volatile component of the photosensitive material is set to 100% by mass, the content of the resin that can be developed using the developing solution is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.
[0185] Unless otherwise specified, the content of each component in a photosensitive material is the value when the non-volatile component in the photosensitive material is set to 100% by mass. The non-volatile component refers to the total non-volatile components in the photosensitive material excluding the solvent.
[0186] Photosensitive materials may contain epoxy resins. For more information on epoxy resins, please refer to the section on [Thermosetting Materials]. Epoxy resins can be used alone or in combination of two or more types.
[0187] From the perspective of improving the strength of cured photosensitive materials, photosensitive materials may contain crosslinking agents. A single crosslinking agent may be used, or two or more may be used in combination.
[0188] Examples of crosslinking agents include compounds containing two or more alkoxymethyl groups in their molecules.
[0189] Examples of compounds containing two or more alkoxymethyl groups in their molecules include amino resins and phenolic resins. Among these, amino resins containing two or more alkoxymethyl groups are preferred for their superior photosensitivity. Examples of amino resins containing two or more alkoxymethyl groups in their molecules include melamine resins and urea resins, with melamine resins being the most preferred.
[0190] Specific examples of melamine resins include Sanwa Chemical's "MW-390", "MW-100LM", "MW-30HM", and "MX-750LM"; and Allnex Japan's CYMEL series. Similarly, specific examples of urea resins include Sanwa Chemical's "MX-270", "MX-279", and "MX-280"; and Allnex Japan's CYMEL series.
[0191] When the non-volatile component of the photosensitive material is set to 100% by mass, the content of the crosslinking agent is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0192] Photosensitive materials may contain photopolymerization initiators. These initiators promote the reaction of resins that can be developed using a developer. A single photopolymerization initiator can be used alone, or two or more can be used in combination.
[0193] Examples of photopolymerization initiators include photoacid generators. These photoacid generators produce acids when irradiated by active light sources such as ultraviolet light. For instance, the generated acids can be used to promote reactions between alkali-soluble resins with phenolic hydroxyl groups and compounds containing two or more alkoxymethyl groups.
[0194] As photoacid generators, compounds that can produce acids upon irradiation with active light can be used. Examples of photoacid generators include halogen-containing compounds, diazonium ketone compounds, sulfone compounds, diazomethane compounds, and diazoquinone compounds.
[0195] Halogenated compounds that can be used as photoacid-generating agents include, for example, hydrocarbon compounds containing halogenated alkyl groups and heterocyclic compounds containing halogenated alkyl groups. Suitable specific examples of halogenated compounds include 2-[2-(furan-2-yl)vinyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(5-methylfuran-2-yl)vinyl]-4,6-bis(trichloromethyl)-s-triazine, 2-(methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-[2-(4-methoxyphenyl)vinyl]-4,6-bis(trichloromethyl)-s- Triazine, 2-[2-(3,4-dimethoxyphenyl)vinyl]-4,6-bis(trichloromethyl)-s-triazine, 1,10-dibromo-n-decane, 1,1-bis(4-chlorophenyl)-2,2,2-trichloroethane, phenylbis(trichloromethyl)-s-triazine, 4-methoxyphenylbis(trichloromethyl)-s-triazine, styryl bis(trichloromethyl)-s-triazine, naphthyl bis(trichloromethyl)-s-triazine, and other s-triazine derivatives. Specific examples of halogenated compounds include "TFE-triazine," "TME-triazine," "MP-triazine," "MOP-triazine," and "dimethoxytriazine" (halogenated compounds with a triazine skeleton are photoacid generators) manufactured by Sanwa Chemical Co., Ltd.
[0196] Examples of diazonone compounds, sulfone compounds, and diazonoquinone compounds include substances described in Japanese Patent Application Publication No. 2018-169627, International Publication No. 2010 / 134207, International Publication No. 2014 / 069202, Japanese Patent Application Publication No. 2020-101813, and International Publication No. 2018 / 232214.
[0197] Other examples of photopolymerization initiators include photoradix generators. When using free radical polymerizable resins, photoradix generators can effectively promote the reaction. Examples of photoradix generators include substances described in documents such as Japanese Patent Application Publication No. 2020-15859, Japanese Patent Application Publication No. 2020-52288, and Japanese Patent Application Publication No. 2018-169627.
[0198] When the non-volatile component in the photosensitive material is set to 100% by mass, the content of the photopolymerization initiator is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, preferably 3% by mass or less, and more preferably 1.5% by mass or less.
[0199] Photosensitive materials may contain thermally generated acid agents. These agents generate acid when the plasma mask is heated, promoting a cross-linking reaction between the resin and the cross-linking agent, which can be developed using a developer. A single thermally generated acid agent can be used alone, or two or more can be used in any ratio.
[0200] Examples of heat-generating acid agents include, for example, onium salt compounds. Examples of onium salt compounds include substances described in documents such as Japanese Patent Application Publication No. 2018-169627.
[0201] When the non-volatile component in the photosensitive material is set to 100% by mass, the content of the thermal acid-generating agent is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, preferably 3% by mass or less, and more preferably 1.5% by mass or less.
[0202] Photosensitive materials may contain adhesion promoters. As adhesion promoters, compounds that enhance the adhesion strength between the insulating material layer and the plasma mask can be used. Adhesion promoters can be used alone or in combination of two or more in any ratio.
[0203] Examples of sealing agents include γ-aminopropyl dimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyl dimethoxysilane, γ-epoxypropoxypropylmethyl dimethoxysilane, γ-mercaptopropylmethyl dimethoxysilane, 3-methacryloyloxypropyl dimethoxymethylsilane, 3-methacryloyloxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, dimethoxymethyl-3-piperidinylpropylsilane, diethoxy-3-epoxypropoxypropylmethylsilane, N-(3-diethoxymethylsilylpropyl)succinimide, N-[3] -(triethoxysilyl)propyl]phthalamide, benzophenone-3,3'-bis(N-[3-triethoxysilyl]propylamide)-4,4'-dicarboxylic acid, benzene-1,4-bis(N-3-triethoxysilyl]propylamide)-2,5-dicarboxylic acid, 3-(triethoxysilyl)propylsuccinic anhydride, N-phenylaminopropyltrimethoxysilane, 3-ureopropyltrimethoxysilane, 3-ureopropyltriethoxysilane, 3-(trialkoxysilyl)propylsuccinic anhydride, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3 -Mercaptopropylmethyldimethoxysilane, mercaptomethyltrimethoxysilane, mercaptomethylmethyldimethoxysilane, 3-mercaptopropyldiethoxymethoxysilane, 3-mercaptopropylethoxydimethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropyldiethoxypropoxysilane, 3-mercaptopropylethoxydipropoxysilane, 3-mercaptopropyldimethoxypropoxysilane, 3-mercaptopropylmethoxydipropoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyldiethoxymethoxysilane, 2-mercaptoethylethoxydimethoxysilane, 2-mercaptoethyltripropoxysilane Silane coupling agents such as 2-mercaptoethyltripropoxysilane, 2-mercaptoethylethoxydipropoxysilane, 2-mercaptoethyldimethoxypropoxysilane, 2-mercaptoethylmethoxydipropoxysilane, 4-mercaptobutyltrimethoxysilane, 4-mercaptobutyltriethoxysilane, 4-mercaptobutyltripropoxysilane, N-(3-triethoxysilylpropyl)urea, N-(3-trimethoxysilylpropyl)urea, and compounds containing an aminotriazine ring and ethoxysilyl group; aluminum-based adhesive additives such as tri(ethyl acetoacetate)aluminum, tri(acetylacetone)aluminum, and ethyl acetoacetate diisopropoxyaluminum.
[0204] The content of the sealing agent relative to 100% by mass of the non-volatile components of the photosensitive material is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less.
[0205] Photosensitive materials may contain organic fillers. Examples of organic fillers include polyurethane particles, rubber particles, polyamide particles, and silicone particles. Polyurethane particles are preferred. Examples of polyurethane particles include "MM-101SW", "MM-101SWA", "MM-101SM", "MM-101SMA", and "MM-110SMA" manufactured by Negami Kogyo Co., Ltd. A single organic filler may be used, or two or more may be used in any ratio.
[0206] The average particle size of the organic filler material is preferably 0.005 μm or more, more preferably 0.2 μm or more, more preferably 1 μm or less, and more preferably 0.6 μm or less. The average particle size of the organic filler material can be determined using a dynamic light scattering method. Specifically, the average particle size of the organic filler material can be determined as follows: the organic filler material is uniformly dispersed in a suitable organic solvent using ultrasound, and the particle size distribution of the organic filler material is prepared according to a mass standard using a thick particle size analyzer (FPAR-1000; manufactured by Otsuka Electronics Co., Ltd.), and the median particle size is taken as the average particle size for measurement.
[0207] When the non-volatile component of the photosensitive material is set to 100% by mass, the content of the organic filler material is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.
[0208] Photosensitive materials may or may not contain inorganic fillers. When a photosensitive material contains inorganic fillers, the content of the inorganic fillers can be less than the lower limit of the content range for inorganic fillers in thermosetting materials; for example, it can be less than 10% by mass relative to 100% by mass of the non-volatile components of the photosensitive material. The content of inorganic fillers in the photosensitive material is generally preferably within the range of inorganic fillers in thermosetting materials.
[0209] When the photosensitive material contains an inorganic filler, the average particle size of the inorganic filler is preferably 0.2 μm or less, more preferably 0.15 μm or less, even more preferably 0.1 μm or less, preferably 0.01 μm or more, more preferably 0.03 μm or more, and particularly preferably 0.05 μm or more.
[0210] In addition to the components mentioned above, photosensitive materials may also contain other additives. Examples of such additives include polymerization inhibitors, defoamers, surfactants, thermoplastic resins, colorants, thickeners, and flame retardants. Furthermore, photosensitive materials may contain any of the components found in thermosetting materials. Other additives may be used individually or in combination of two or more.
[0211] Photosensitive materials may contain solvents as volatile components. These solvents are the same as those that may be contained in thermosetting materials.
[0212] The photosensitive material may contain a solvent, preferably in a small amount. The amount of solvent contained in the photosensitive material is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, relative to 100% by mass of the non-volatile components in the photosensitive material.
[0213] The preparation method of the photosensitive material is not particularly limited, and examples include methods such as using a mixing apparatus or a stirring apparatus to mix / disperse the compounding components with a solvent as needed. A suitable embodiment of the photosensitive material is a negative photosensitive material containing a polyimide precursor and capable of being developed using a solvent, i.e., a solvent-developable negative photosensitive polyimide resin. The photosensitive material is preferably in liquid form.
[0214] Commercially available photosensitive materials can be used. Examples of commercially available products include "SU-83010" manufactured by Nippon Kayaku Co., Ltd.
[0215] Cured photosensitive materials typically exhibit a high glass transition temperature (Tg). Therefore, when using this cured material to form a plasma mask, a plasma mask with a high glass transition temperature can be obtained. The glass transition temperature of the cured material is preferably 130°C or higher, more preferably 140°C or higher, and even more preferably 150°C or higher. There is no particular upper limit; for example, it can be set to 400°C or lower. The glass transition temperature can be measured using the method described in the examples below.
[0216] Cured photosensitive materials typically exhibit a low coefficient of linear thermal expansion (CTE). Therefore, when using this cured material to form a plasma mask, a plasma mask with a low CTE can be obtained. The CTE of the cured material is preferably 100 ppm / °C or less, more preferably 80 ppm / °C or less, and even more preferably 75 ppm / °C or less. The lower limit is not particularly limited, and for example, it can be set to 0.01 ppm / °C or more. The CTE can be measured using the method described in the examples below.
[0217] Cured photosensitive materials typically exhibit a high elastic modulus at 23°C. Therefore, plasma masks with excellent crack resistance can be obtained. The elastic modulus of the cured material at 23°C is preferably 1.0 GPa or higher, more preferably 1.5 GPa or higher, and even more preferably 2.0 GPa or higher. There is no particular upper limit, and it can be set to 50 GPa or lower, etc. The elastic modulus can be measured using the method described in the examples below.
[0218] Cured photosensitive materials typically exhibit high elongation (elongation at break). Therefore, plasma masks with high elongation at break can be obtained. The elongation at break of the cured material is preferably 10% or more, more preferably 20% or more, and particularly preferably 30% or more. There is no particular upper limit; for example, it can be 80% or less, 70% or less, 60% or less, etc. The elongation can be measured according to the method described in the examples below.
[0219] In this invention, the elongation at break of the cured photosensitive material is preferably greater than that of the cured thermosetting material.
[0220] Cured photosensitive materials typically exhibit a low dielectric loss tangent. Therefore, plasma masks with low dielectric loss tangents can be obtained. The dielectric loss tangent of the cured material is preferably 0.05 or less, more preferably 0.04 or less, and even more preferably 0.03 or less. The lower limit of the dielectric loss tangent is not particularly limited, and for example, it can be 0.0005 or more. The dielectric loss tangent can be measured using the method described in the examples below.
[0221] Cured photosensitive materials typically exhibit a low relative permittivity. Therefore, plasma masks with low relative permittivity can be obtained. The permittivity of the cured material is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.5 or less. The lower limit is not particularly limited; for example, it can be set to 0.0001 or more. The relative permittivity can be measured using the method described in the examples below. In this invention, the relative permittivity of both the cured photosensitive material and the cured thermosetting material is preferably 3.5 or less.
[0222] [Thermosetting resin sheets and photosensitive resin sheets]
[0223] Thermosetting resin sheet comprises a support and a thermosetting material layer formed of thermosetting material disposed on the support. The thermosetting material is as described in the [Thermosetting Material] section.
[0224] The photosensitive resin sheet includes a support and a photosensitive material layer formed of a photosensitive material disposed on the support. The photosensitive material is as described in the [Photosensitive Material] section.
[0225] Hereinafter, thermosetting material layers and photosensitive material layers will sometimes be referred to as "material layers", and thermosetting resin sheets and photosensitive resin sheets will sometimes be referred to as "resin sheets".
[0226] From the perspective of achieving thinner printed wiring boards and providing a cured material with excellent insulation even when the cured thermosetting material layer is a thin film, the thickness of the thermosetting material layer is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 40 μm or less, 30 μm or less, or 20 μm or less. The lower limit of the thickness of the thermosetting material layer is not particularly limited, and can typically be set to 1 μm or more, 3 μm or more, etc.
[0227] From the viewpoint of achieving significant effects of the present invention, the thickness of the photosensitive material layer is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 40 μm or less. From the viewpoint of leaving it as a plasma mask on the insulating material layer, the lower limit of the thickness of the photosensitive material layer is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0228] Examples of supports include films containing plastic materials, metal foils, and release paper, with films and metal foils containing plastic materials being preferred.
[0229] When using a film containing plastic materials as a support, examples of plastic materials include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"); acrylics such as polycarbonate (hereinafter sometimes abbreviated as "PC") and polymethyl methacrylate (PMMA); cyclic polyolefins; cellulose triacetate (TAC); polyether sulfide (PES); polyether ketone; and polyimide. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0230] When using metal foil as a support, examples of metal foil include copper foil and aluminum foil, with copper foil being preferred. Copper foil can be used as the support, either as a foil containing elemental copper or as an alloy of copper with other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0231] The surfaces of the support body that are joined to the material layer can be treated with matte finish, corona treatment, and antistatic treatment.
[0232] Additionally, as a support, a support with a release layer can be used on the surface that bonds to the material layer. The release agent used in the release layer of the support with the release layer can be, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins. Commercially available products can be used as supports with release layers, such as PET films with release layers that have an alkyd resin-based release agent as the main component, such as LINTEC's "SK-1," "AL-5," and "AL-7," Toray's "Lumirror T60," Teijin's "PUREX," and UNITIKA's "UNIPEEL"; and DUPONT FILM's "U2-NR1," etc.
[0233] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. It should be noted that when using a support with a release layer, the overall thickness of the support with the release layer is preferably within the above range.
[0234] In one embodiment, the resin sheet may further include other layers as needed. Examples of such other layers include, for instance, a protective film based on the support body disposed on the side of the material layer that is not in contact with the support body (i.e., the side opposite to the support body). The thickness of the protective film is not particularly limited, for example, from 1 μm to 40 μm. By laminating the protective film, it is possible to suppress the adhesion and damage of contaminants and other pollutants to the surface of the material layer.
[0235] Resin sheets can be manufactured, for example, as follows: a resin varnish containing a thermosetting or photosensitive material dissolved in an organic solvent is prepared; the resin varnish is then applied to a support using a die coater or similar machine, and further dried to form a material layer. The solvents described above can be used.
[0236] Drying can be carried out by known methods such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is achieved when the content of organic solvent in the material layer is 10% by mass or less, preferably 5% by mass or less. The method also varies depending on the boiling point of the organic solvent in the resin varnish. For example, when using a resin varnish containing 30% to 60% by mass of organic solvent, a material layer can be formed by drying it at 50°C to 150°C for 3 to 10 minutes.
[0237] The resin sheets can be stored in rolls. If the resin sheet has a protective film, it can be used by peeling off the protective film.
[0238] [Prepreg]
[0239] The prepreg is formed by impregnating the aforementioned thermosetting material into a sheet fiber substrate.
[0240] The sheet fiber substrate used in the prepreg can be, for example, glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, or other commonly used substrates for prepregs. From the viewpoint of thinning the wiring board, the thickness of the sheet fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the sheet fiber substrate thickness is not particularly limited, and is generally 10 μm or more. The thickness of the prepreg can be within the same range as the sheet fiber substrate described above.
[0241] Prepregs can be manufactured using methods such as hot-melt method and solvent method.
[0242] [Manufacturing method of wiring board]
[0243] A first embodiment of the wiring board manufacturing method of the present invention includes:
[0244] (1) A process of preparing a substrate having a conductor circuit and an insulating material layer formed by a cured thermosetting material on the conductor circuit, and applying or both of photosensitive material coating and pasting to the surface of the insulating material layer to form a photosensitive material layer.
[0245] (2) The process of exposing and developing the photosensitive material layer to form a plasma mask with an opening;
[0246] (3) A process of irradiating an insulating material layer with plasma through a plasma mask, forming either or both of vias and trenches in the insulating material layer at the opening of the plasma mask, and performing a sublimation process on the plasma mask; and
[0247] (4) The process of forming a conductor layer on the surface of a subtractive plasma mask and any one or both of vias and trenches.
[0248] In the above description, conventional methods for forming vias or trenches in insulating material layers involve forming a mask, such as a dry film or metal foil, on the insulating material layer, patterning the mask to form a mask pattern, performing plasma treatment or laser treatment over the mask pattern, and then peeling off or removing the mask pattern. In the wiring board manufacturing method of the present invention, a plasma mask equivalent to the conventional mask pattern remains as a base layer (permanent film), thus eliminating the need for mask pattern removal as in the past. In the present invention, since the plasma mask remains directly, chemical damage to the insulating material layer caused by stripping fluids or the like used when removing the mask pattern can be suppressed. As a result, the insulating material layer exhibits excellent insulation and electrical properties, improving insulation performance after HAST testing. In particular, cured thermosetting materials tend to have superior insulation and electrical properties compared to cured photosensitive materials. Therefore, the combination of an insulating material layer formed from a cured thermosetting material and a plasma mask formed from a cured photosensitive material can efficiently improve insulation and electrical properties. In addition, since a photosensitive material layer is formed on the insulating material layer, it is easy to align the mask pattern and form small-diameter through holes or small-diameter trenches.
[0249] <Process (1)>
[0250] In step (1), a substrate with an insulating material layer is prepared on an inner circuit substrate having a conductor circuit. A photosensitive material layer is formed by coating and bonding (lamination) of a photosensitive material onto the insulating material layer of this substrate. In step (1), as... Figure 1 As shown in the example, a substrate 10 is prepared to form an insulating material layer 11 on the conductor circuit of an inner layer circuit substrate 12 in which conductor circuits (not shown) are formed. From the viewpoint of significantly obtaining the effects of the present invention, the insulating material layer 11 comprises a cured thermosetting material.
[0251] When performing step (1), the process may include (1-1) preparing an inner layer circuit board on which conductive circuits are formed. The inner layer circuit board on which conductive circuits are formed typically includes a support substrate and a metal layer disposed on the surface of the support substrate. The metal layer typically protrudes to the surface of the inner layer circuit board and functions as a conductive circuit.
[0252] Examples of materials that can be used as the support substrate include glass epoxy boards, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates. Examples of materials that can be used as the metal layer include copper foil, copper foil with a carrier, and materials for the conductor layer described later, with copper foil being the most preferred.
[0253] The conductor circuit can be formed by the same method as the formation of the conductor layer in step (4) described later.
[0254] When the conductor circuit is a patterned conductor circuit, from the viewpoint of fine wiring, the line (conductor layer width) / spacing (width between conductor layers) ratio (L / S), i.e., the wiring spacing of the conductor circuit, is preferably 5μm / 5μm or less (i.e., wiring spacing of 10μm or less), more preferably 4μm / 4μm or less (wiring spacing of 8μm or less), and even more preferably 3μm / 3μm or less (wiring spacing of 6μm or less). The lower limit of the line / spacing ratio of the conductor circuit is preferably 0.1μm / 0.1μm or more (wiring spacing of 0.2μm or more), more preferably 0.5μm / 0.5μm or more (wiring spacing of 1μm or more), and even more preferably 1μm / 1μm or more (wiring spacing of 2μm or more). The wiring spacing does not necessarily need to be the same throughout the conductor circuit.
[0255] When performing step (1), it may include (1-2) forming a thermosetting material layer on the conductor circuit of the inner circuit board, and then thermally curing the thermosetting material layer to form an insulating material layer. Examples of methods for forming the insulating material layer include: forming a thermosetting material layer by directly coating a thermosetting material on the conductor circuit of the inner circuit board and then thermally curing it; forming an insulating material layer by attaching (laminating) a thermosetting resin sheet on the conductor circuit of the inner circuit board and then thermally curing the thermosetting material layer; and forming an insulating material layer by laminating a prepreg on the conductor circuit of the inner circuit board and then thermally curing it. From the viewpoint of significantly obtaining the effects of the present invention, step (1-2) is preferably a step of laminating a thermosetting material layer of a thermosetting resin sheet on the conductor circuit of the inner circuit board and then thermally curing the thermosetting material layer to form an insulating material layer. The thermosetting material, thermosetting resin sheet, and prepreg are as described above. In addition, the insulating material layer can be a single layer or multiple layers stacked together.
[0256] The lamination of the inner circuit board and the thermosetting resin sheet can be achieved, for example, by heating and pressing the thermosetting resin sheet onto the inner circuit board from the support side. Examples of components for heating and pressing the thermosetting resin sheet onto the inner circuit board (hereinafter also referred to as "heat-pressing components") include, for example, heated metal plates (SUS mirror plates, etc.) or metal rollers (SUS rollers). It should be noted that it is preferable that the heat-pressing components are not directly pressed onto the thermosetting resin sheet, but rather that pressure is applied through an elastic material such as heat-resistant rubber, so that the thermosetting resin sheet fully conforms to the surface irregularities of the inner circuit board.
[0257] The lamination of the inner circuit board and the thermosetting resin sheet can be performed by vacuum lamination. In vacuum lamination, the heating and pressing temperature is preferably in the range of 60°C to 160°C, more preferably 80°C to 140°C; the heating and pressing pressure is preferably in the range of 0.098 MPa to 1.77 MPa, more preferably 0.29 MPa to 1.47 MPa; and the heating and pressing time is preferably in the range of 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. Lamination is preferably performed under reduced pressure conditions of 26.7 hPa or less.
[0258] Lamination can be performed using commercially available vacuum laminators. Examples of commercially available vacuum laminators include, for instance, the vacuum pressure laminator manufactured by Meiki Seisakusho, the vacuum applicator manufactured by NIKKO MATERIALS, and intermittent vacuum pressure laminators.
[0259] After lamination, the laminated thermosetting resin sheets can be smoothed by applying pressure to the heated pressing members under normal pressure (atmospheric pressure), for example, from the support side. The pressure conditions for smoothing can be set to the same conditions as the heated pressing conditions for lamination described above. The smoothing process can be performed using a commercially available laminator. It should be noted that lamination and smoothing can be performed continuously using the aforementioned commercially available vacuum laminator.
[0260] The support can be removed after the thermosetting resin sheet is laminated and before it is thermally cured, or it can be removed after the thermosetting material layer is thermally cured, or it can be removed before the photosensitive material layer is formed on the insulating material layer.
[0261] After a thermosetting resin sheet is laminated onto the inner circuit board, the thermosetting material layer is thermally cured to form an insulating material layer. The thermal curing conditions for the thermosetting material layer are not particularly limited; conditions typically used when forming insulating material layers for printed wiring boards can be used.
[0262] For example, the curing conditions of the thermosetting material layer vary depending on the type of thermosetting material, etc. The curing temperature is preferably 120℃~240℃, more preferably 150℃~220℃, and even more preferably 170℃~210℃. The curing time can preferably be set to 5 minutes~120 minutes, more preferably 10 minutes~100 minutes, and even more preferably 15 minutes~100 minutes.
[0263] Before heat curing the thermosetting material layer, the thermosetting material layer can be preheated at a temperature lower than the curing temperature. For example, before heat curing the thermosetting material layer, the thermosetting material layer can be preheated for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes) at a temperature of 50°C or higher and lower than 120°C (preferably 60°C or higher and lower than 115°C, more preferably 70°C or higher and lower than 110°C) to a temperature of 50°C or higher and lower than 120°C.
[0264] The thickness of the insulating material layer is preferably less than 100 μm, more preferably less than 50 μm, even more preferably less than 40 μm, less than 30 μm, less than 20 μm, preferably more than 1 μm, and more preferably more than 3 μm.
[0265] When a thermosetting material is directly coated onto the conductor circuit of an inner layer circuit board to form an insulating material layer, the conditions for forming the insulating material layer are the same as those for forming an insulating material layer using a thermosetting resin sheet. Examples of coating methods for thermosetting materials include wire rod coating, reverse coating, gravure coating, die coating, blade coating, dip coating, air knife coating, curtain coating, and roller coating. Furthermore, when a prepreg is used to form the insulating material layer, the conditions for forming the insulating material layer are the same as those for forming an insulating material layer using a thermosetting resin sheet.
[0266] In addition, in process (1), such as Figure 2 As illustrated in the example, the process includes: (1-3) either or both of coating and pasting a photosensitive material onto the surface of the insulating material layer 11 to form a photosensitive material layer 20. Details of the photosensitive material layer 20 may include: a method of forming a photosensitive material layer by directly coating a photosensitive material onto the surface of the insulating material layer; and a method of pasting (laminating) a photosensitive resin sheet having the photosensitive material layer onto the surface of the insulating material layer. The photosensitive material and the photosensitive resin sheet are as described above. The photosensitive material layer can be a single layer or multiple layers.
[0267] The absolute value of the difference between the linear thermal expansion coefficient of the cured photosensitive material (plasma mask) and the linear thermal expansion coefficient of the cured thermosetting material (insulating material layer) is preferably 60 ppm / ℃ or less, more preferably 55 ppm / ℃ or less, and even more preferably 50 ppm / ℃ or less. The lower limit is not particularly limited, but is preferably 0 ppm / ℃ or more, more preferably 0.5 ppm / ℃ or more, and even more preferably 1 ppm / ℃ or more. By selecting a photosensitive material (when forming the photosensitive material layer 20 using a photosensitive resin sheet) such that the absolute value of the difference between the linear thermal expansion coefficients of the cured photosensitive materials falls within this range, the effects of the present invention can be significantly obtained.
[0268] The absolute value of the difference between the glass transition temperature (Tg) of the photosensitive material that may be included in the plasma mask and the glass transition temperature (Tg) of the thermosetting material that may be included in the insulating material layer is preferably 100°C or less, more preferably 90°C or less, and even more preferably 80°C or less. The lower limit is not particularly limited, but it is preferably 0°C or more, more preferably 0.5°C or more, and even more preferably 1°C or more. By selecting the photosensitive material (when the photosensitive material layer 20 is formed using a photosensitive resin sheet) such that the absolute value of the difference in glass transition temperatures of the cured photosensitive material falls within this range, the effects of the present invention can be significantly obtained.
[0269] The coefficient of linear thermal expansion of the composite material obtained by laminating a cured photosensitive material (plasma mask) and a cured thermosetting material (insulating material layer) is preferably 100 ppm / ℃ or less, more preferably 50 ppm / ℃ or less, and even more preferably 45 ppm / ℃ or less. The lower limit is not particularly limited and can be set to 1 ppm / ℃ or more, 10 ppm / ℃ or more, etc. By selecting the photosensitive material (a photosensitive material layer when forming the photosensitive material layer 20 using a photosensitive resin sheet) and the thermosetting material (a thermosetting material layer when forming the insulating material layer using a thermosetting resin sheet) such that the overall coefficient of linear thermal expansion falls within this range, the effects of the present invention can be significantly obtained.
[0270] The lamination conditions of the insulating material layer and the photosensitive resin sheet can be the same as those of the inner circuit board and the thermosetting resin sheet.
[0271] When a photosensitive material layer is formed by directly coating a photosensitive material onto the surface of an insulating material layer, the coating method for the photosensitive material can be the same as the coating method for directly coating a thermosetting material onto the conductor circuit of an inner circuit board. In this case, the photosensitive material is preferably in a liquid state.
[0272] The thickness of the photosensitive material layer is the same as the thickness of the photosensitive material layer in the photosensitive resin film.
[0273] <Process (2)>
[0274] In process (2), such as Figure 3 As shown in the example, the photosensitive material layer 20 is irradiated with active energy rays, and then exposed and developed to form a plasma mask 21 with an opening 211. Details regarding the exposure are available through... Figure 3 A photomask (not shown) is used to irradiate the surface of the photosensitive material layer with active energy rays, causing the photosensitive material layer to solidify. In step (2), as... Figure 9 As shown in the example, a plasma mask 21 with multiple openings 211 can be formed.
[0275] Examples of active energy rays include ultraviolet light, visible light, electron beams, and X-rays, with ultraviolet light being preferred. The amount and duration of ultraviolet irradiation can be appropriately set according to the photosensitive material layer. Examples of exposure methods include, for instance, contact exposure, where the mask pattern is tightly adhered to the photosensitive material layer and then exposed; and non-contact exposure, where the mask pattern is not tightly adhered to the photosensitive material layer but rather exposed using parallel light.
[0276] After exposure, the exposed or unexposed portions of the photosensitive material layer are removed by development to form a plasma mask. Development can be performed using either wet or dry development. Examples of development methods include immersion, paddle, spray, brushing, and scraping.
[0277] In step (2), if necessary, plasma treatment can be used to remove residues such as adhering substances remaining on the surface of the plasma mask after development.
[0278] From the viewpoint of achieving significant effects of the present invention, the thickness of the plasma mask is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less.
[0279] When the thickness of the plasma mask after step (2) is set to T1 (μm) and the thickness of the insulating material layer after step (2) is set to T2 (μm), from the viewpoint of significantly obtaining the effect of the present invention, it is preferable to satisfy the relationship T1>T2.
[0280] <Process (3)>
[0281] In process (3), such as Figure 4 As shown in the example, plasma irradiation is performed on the insulating material layer 11 through the plasma mask 21, forming either or both of vias 30 and trenches (not shown) in the insulating material layer 11 at the opening 211 of the plasma mask 21, and simultaneously etching of the plasma mask 21 is performed to reduce the thickness of the plasma mask 21. Figure 5 As shown in the example, after process (3) is completed, the plasma mask 21 is etched by plasma irradiation, resulting in a reduction film, but remains on the insulating material layer 11 as a base layer (permanent film).
[0282] When the thickness of the plasma mask before plasma irradiation is set to 1, from the viewpoint of significantly obtaining the effects of the present invention, the thickness of the plasma mask after plasma irradiation, that is, the thickness of the plasma mask after the reduction film after process (3), is preferably 0.01 or more, more preferably 0.05 or more, further preferably 0.1 or more, or 0.15 or more. Preferably 0.7 or less, more preferably 0.6 or less, and further preferably 0.5 or less. It should be noted that in conventional wiring board manufacturing methods, the mask is removed or peeled off after forming through holes or trenches. Therefore, when the thickness of the mask before plasma treatment is set to 1, the thickness of the mask after plasma treatment is at most 0.05.
[0283] From the viewpoint of achieving significant effects of the present invention, the thickness of the plasma mask after the reduction film is completed after step (3) is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less.
[0284] From the viewpoint of achieving significant effects of the present invention, the total thickness of the plasma mask and the insulating material layer after the reduction film is completed in step (3) is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 13 μm or less, preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0285] Regarding the plasma treatment in step (3), plasma generated by introducing gas into a plasma generator is used to treat the surfaces of the insulating material layer and the plasma mask located at the opening. As a result, through holes or trenches are formed on the surface of the insulating material layer located at the opening, and the plasma mask is reduced in thickness by etching. There are no particular limitations on the method of plasma generation, and examples include: microwave plasma generated using microwaves, high-frequency plasma obtained using high frequency, atmospheric pressure plasma generated under atmospheric pressure, atmospheric pressure plasma generated under vacuum, etc. Atmospheric pressure plasma generated under vacuum is preferred.
[0286] In addition, the plasma used in step (3) is preferably RF plasma excited by high frequency.
[0287] The gas used for plasma generation is preferably a gas containing at least one of Ar, O2, CF4 and SF6, and more preferably a mixture of O2 and CF4.
[0288] The mixing ratio of the mixed gas containing O2 and CF4 (CF4 / O2: in sccm) is preferably 99 / 1 to 1 / 99, more preferably 90 / 10 to 30 / 70, and even more preferably 90 / 10 to 70 / 30, from the viewpoint of making the thickness of the conductor layer formed in the through hole or trench uniform.
[0289] The plasma irradiation time in plasma treatment is not particularly limited, but is preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 3 minutes or more. Regarding the upper limit, there is no particular limitation, but is preferably 120 minutes or less, even more preferably 100 minutes or less, and even more preferably 60 minutes or less.
[0290] This invention forms through-holes or trenches in the insulating material layer at the opening of a plasma mask through plasma treatment, thereby reducing the opening diameter of the through-holes or trenches. The aforementioned opening diameter is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. The lower limit is not particularly limited and can be set to 1 μm or more, etc.
[0291] From the viewpoint of achieving significant effects of the present invention, the etching rate based on plasma irradiation is preferably 100 nm / min or higher, more preferably 110 nm / min or higher, and even more preferably 120 nm / min or higher. There is no particular upper limit, but it is preferably 2000 nm / min or lower, more preferably 1500 nm / min or lower, and even more preferably 1000 nm / min or lower.
[0292] This invention forms through-holes or trenches through plasma treatment, thus enabling the hole cone angle of the through-hole or trench to be approximately 90 degrees. The hole cone angle is preferably 65 degrees or more, more preferably 70 degrees or more, and even more preferably 72 degrees or more. There is no particular upper limit, but it is preferably 90 degrees or less, more preferably 88 degrees or less, and even more preferably 85 degrees or less. The hole cone angle refers to the angle formed between the wall surface of the through-hole or trench and the bottom of the hole.
[0293] From the viewpoint of achieving significant effects of the present invention, the arithmetic mean roughness (Ra) of the plasma mask surface after plasma treatment with subtractive coating is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 60 nm or less. The lower limit is not particularly limited and can be set to 1 nm or more, 10 nm or more, etc. The arithmetic mean roughness can be measured by the method described in the embodiments below.
[0294] From the viewpoint of significantly obtaining the effects of the present invention, the roughness (Sa) of the wall surface of the through hole or trench after plasma treatment is preferably 400 nm or less, more preferably 350 nm or less, and further preferably 300 nm or less. The lower limit is not particularly limited and can be set to 110 nm or more, 150 nm or more, etc. The roughness (Sa) represents the arithmetic mean height defined in ISO 25178 and can be measured by the method described in the examples below.
[0295] From the viewpoint of significantly obtaining the effects of the present invention, the ratio (Ra / Sa) of the arithmetic mean roughness (Ra) of the surface of the plasma mask after film reduction after plasma treatment to the roughness (Sa) of the wall surface of the through hole or trench after plasma treatment is preferably 3 or less, more preferably 2 or less, further preferably 1 or less, 0.5 or less, and preferably 0.01 or more, more preferably 0.05 or more, and further preferably 0.1 or more.
[0296] From the viewpoint of significantly obtaining the effects of the present invention, the hole expansion rate is preferably 150% or less, more preferably 145% or less, and further preferably 140% or less, and preferably 100% or more, further preferably 105% or more, and more preferably 110% or more. The hole expansion rate means that when the bottom diameter of the pattern of the plasma mask after the end of step (2) is set to 100%, the ratio represents how much the diameter of the boundary between the plasma mask and the insulating material layer in the through hole or trench after the end of step (3) expands. More than 100% means the diameter expands, and less than 100% means the diameter contracts. In the present invention, even when plasma treatment is performed in step (3), the bottom diameter of the pattern of the plasma mask is suppressed from becoming too large, and thus, fine wiring can be achieved. The hole expansion rate can be measured by the method described in the examples below.
[0297] When the thickness of the plasma mask after film reduction after the end of step (3) is set to T3 (μm) and the thickness of the insulating material layer after the end of step (3) is set to T4 (μm), from the viewpoint of significantly obtaining the effects of the present invention, it is preferable to satisfy the relationship of T3 < T4.
[0298] <Step (4)>
[0299] Step (4) is the process of forming a conductor layer on the surface of either or both of the subtractive plasma mask and the vias and trenches exposed to the openings of the plasma mask. Details of the conductor layer include either or both of the conductor wiring formed outside the openings of the plasma mask and the conductor via layers formed in the openings of the plasma mask. The conductor material used in the conductor layer is not particularly limited. In a suitable embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor layer can be a single metal layer or an alloy layer. Examples of alloy layers include, for instance, layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloys, copper-nickel alloys, and copper-titanium alloys). From the perspective of the versatility, cost, and ease of patterning of the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy, is preferred. More preferably, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of nickel-chromium alloy is preferred.
[0300] The conductor layer can be a single-layer structure, or a multi-layer structure consisting of two or more single-metal layers or alloy layers of different types of metals or alloys. When the conductor layer is a multi-layer structure, the layer in contact with either the via or the trench is preferably a single-metal layer of chromium, zinc, or titanium, or an alloy layer of nickel-chromium alloy.
[0301] The thickness of the conductor layer depends on the desired printed wiring board design, typically 3μm to 35μm, preferably 5μm to 30μm.
[0302] The conductor layer can be formed by any suitable method known in the art, such as plating, sputtering, or evaporation, preferably by plating. In a suitable embodiment, a patterned conductor layer with a desired wiring pattern is formed by plating the surface of a subtractive plasma mask and any or both of vias and trenches using known techniques such as semi-additive or fully additive methods.
[0303] When performing process (4), such as Figure 6As shown in the example, the process may include: (4-1) forming a plating seed layer 41 on the surface of the subtractive plasma mask 21 and on the surface of either or both of the via 30 and the trench (not shown). The plating seed layer can be formed by dry plating or by wet plating. Examples of dry plating include physical vapor deposition (PVD) methods such as sputtering, ion plating, and vacuum evaporation; and chemical vapor deposition (CVD) methods such as thermal CVD and plasma CVD. Examples of wet plating include electroless plating. In step (4-1), the plating seed layer is preferably formed by dry plating, and from the viewpoint of enabling micro-wiring, it is more preferable to form the plating seed layer by sputtering.
[0304] When forming a conductor layer by sputtering, typically, a conductor seed layer is first formed by sputtering onto the surface of a subtractive plasma mask and the surface of either or both of vias and trenches, and then a conductor sputtered layer is formed on the conductor seed layer by sputtering. Before forming the conductor seed layer by sputtering, the surface of the subtractive plasma mask and the surface of either or both of vias and trenches can be cleaned by backsputtering. Additionally, in the case of trenches, an arbitrary anti-diffusion layer can be provided to improve insulation reliability. Various gases can be used as the gas used in this backsputtering, among which Ar, O2, and N2 are preferred. When the seed layer is Cu and Cu alloys, Ar or O2 or a mixture of Ar and O2 is preferred; when the seed layer is Ti, Ar or N2 or a mixture of Ar and N2 is preferred; and when the seed layer is Cr and Cr alloys (nickel-chromium alloys, etc.), Ar or O2 or a mixture of Ar and O2 is preferred. Sputtering can be performed using various sputtering apparatuses such as magnetron sputtering and mirror sputtering. Examples of metals used to form the conductor seed layer include Cr, Ni, Ti, and nickel-chromium alloys. Cr and Ti are particularly preferred. The conductor seed layer is typically formed with a thickness of 5 nm or more, more preferably 10 nm or more, more preferably 1000 nm or less, and even more preferably 500 nm or less. Examples of metals used to form the conductor sputtered layer include Cu, Pt, Au, and Pd. Cu is particularly preferred. The conductor sputtered layer is typically formed with a thickness of 50 nm or more, more preferably 100 nm or more, more preferably 3000 nm or less, and even more preferably 1000 nm or less.
[0305] When forming the conductor seed layer, the surface roughness (Ra value) formed on the surface of the plasma mask after the film is removed, as well as on the surface of any one or both of the vias and trenches, is preferably 150 nm or less, more preferably in the range of 10 to 150 nm, and even more preferably 10 to 120 nm or less, measured after the conductor seed layer is removed by etching.
[0306] After forming the coating seed layer 41 by sputtering, as Figure 7 As shown in one example, it may also include: (4-2) a step of depositing a conductor layer on the deposited seed layer 41 to form a conductor layer. Specifically, after forming the deposited seed layer, a mask pattern (not shown) is formed that exposes a portion of the deposited seed layer. The mask pattern can be formed, for example, by bonding a dry film to the deposited seed layer and then exposing, developing, and cleaning it under specified conditions. In the case of trench-filled wiring, the wiring can be formed by polishing using a polishing process such as CMP after filling the trench with deposited material.
[0307] As a dry film, a photosensitive dry film containing a photoresist composition can be used. Examples of such dry films include dry films made of phenolic varnish resin, acrylic resin, etc. Commercially available dry films can be used, such as "PHOTEC RY-5115" manufactured by RESONAC Corporation, and "ALPHO 20A263" manufactured by NIKKOMATERIALS Corporation.
[0308] Next, an electroplating layer 42 is formed on the exposed plating seed layer 41 by electroplating. In the case of either or both of through holes and trenches, the electroplating layer 42 can be formed on the exposed plating seed layer 41 by electroplating, and either or both of the through holes and trenches can be filled by electroplating to form a hole filler.
[0309] After the electroplated coating 42 is formed, as Figure 8 As shown in one example, the conductor layer 40 is formed by removing the mask pattern (not shown) and removing the unwanted plating seed layer 41 using an etching process such as rapid etching. Additionally, after removing the mask pattern, an annealing process may be performed if necessary. Figure 8 In the middle, the conductor layer 40 forms a patterned conductor layer, but it can be an unpatterned conductor layer.
[0310] Mask patterns can be removed using alkaline stripping solutions such as sodium hydroxide solution.
[0311] Annealing can be performed, for example, by heating the inner layer substrate at 150–200°C for 20–90 minutes.
[0312] Rapid etching is typically performed using etchants such as etching solutions. For example, when the material of the patterned conductor layer is copper, examples of etchants include those with hydrogen peroxide as the main component (hydrogen peroxide-based etchants), acidic etchants, and alkaline etchants.
[0313] From the viewpoint of achieving significant effects of the present invention, the temperature of the etching solution is preferably 5°C or higher, more preferably 10°C or higher, even more preferably 15°C or higher, preferably 60°C or lower, more preferably 50°C or lower, and even more preferably 40°C or lower.
[0314] From the viewpoint of thinning, the thickness of the conductor layer is preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more.
[0315] When the conductor layer is a patterned conductor layer, from the viewpoint of microwiring, the line width (conductor layer width) of the patterned conductor layer is preferably 5 μm or less, more preferably 4 μm, and even more preferably 3 μm. The lower limit of the conductor layer line width is not particularly limited, but is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more.
[0316] When the conductor layer is a patterned conductor layer, from the viewpoint of microwiring, the spacing between the patterned conductor layers (the width between conductor layers) is preferably 5 μm or less, more preferably 4 μm, and even more preferably 3 μm. The lower limit of the line width of the conductor layer is not particularly limited, but is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more.
[0317] When the conductor layer is a patterned conductor layer, from the viewpoint of fine wiring, the line (conductor layer width) / spacing (width between conductor layers) (L / S) ratio of the patterned conductor layer is preferably 5 μm / 5 μm or less (i.e., a pattern with a wiring spacing of 10 μm or less), more preferably 4 μm / 4 μm or less (a pattern with a wiring spacing of 8 μm or less), and even more preferably 3 μm / 3 μm or less (a pattern with a wiring spacing of 6 μm or less). The lower limit of the line / spacing ratio of the conductor layer is preferably 0.1 μm / 0.1 μm or more (a pattern with a wiring spacing of 0.2 μm or more), more preferably 0.5 μm / 0.5 μm or more (a pattern with a wiring spacing of 1 μm or more), and even more preferably 1 μm / 1 μm or more (a pattern with a wiring spacing of 2 μm or more). The wiring spacing does not necessarily have to be the same throughout the conductor layer.
[0318] When manufacturing a wiring board, processes (1) to (4) can be repeated as needed to form a multilayer wiring board.
[0319] The wiring board obtained by the wiring board manufacturing method of the first embodiment is as follows: Figure 8 As shown in the example, it is preferred to form a conductor circuit, an insulating material layer, a plasma mask and a conductor layer in that order and have a via, and more preferably to include two or more conductor circuits, insulating material layers, plasma masks, conductor layers and vias.
[0320] In the first embodiment, for ease of explanation, according to Figures 4-8 The first embodiment is described using only a through hole 30, but it may have both a through hole 30 and a groove 31, or only a groove. Specifically, as... Figure 10 As shown in the example, plasma irradiation is performed on the insulating material layer 11 through the plasma mask 21, forming either or both of vias 30 and trenches 31 in the insulating material layer 11 at the opening 211 of the plasma mask 21. Simultaneously, the plasma mask 21 is etched, causing a reduction film formation in the plasma mask 21. Figure 11 As shown in the example, the plasma mask 21 remains on the insulating material layer 11 as a substrate layer (permanent film). And, as... Figure 12 As shown in one example, a plating seed layer 41 is formed on the surface of the subtractive plasma mask 21 and on the surface of either or both of the vias 30 and trenches 31, such as Figure 13 As shown in the example, plating is further performed on the plating seed layer 41. Figure 14 As shown in the example, the unwanted plating seed layer 41 is removed by using an etching process such as rapid etching, thereby forming the conductor layer 40.
[0321] A second embodiment of the wiring board manufacturing method of the present invention includes:
[0322] (A) A process of preparing a substrate having a conductor circuit and an insulating material layer formed on the conductor circuit by a cured thermosetting material, and applying or both of coating and pasting a first photosensitive material to the surface of the insulating material layer to form a first photosensitive material layer.
[0323] (B) The process of exposing and developing the first photosensitive material layer to form a first plasma mask with an opening;
[0324] (C) A process of irradiating an insulating material layer with plasma through a first plasma mask, forming either or both of a via and a trench in the insulating material layer at the opening of the plasma mask, and performing a reduction film process on the plasma mask.
[0325] (D) A process of forming a second photosensitive material layer by coating and pasting a second photosensitive material in a manner that covers the surface and opening of a first plasma mask.
[0326] (E) The process of exposing and developing the second photosensitive material layer to form a second plasma mask with an opening;
[0327] (F) The process of irradiating a first plasma mask and an insulating material layer with plasma through a second plasma mask to form either or both of a through hole and a trench in the insulating material layer;
[0328] (G) The process of forming a conductor layer on the surface of the first plasma mask and either or both of the vias and trenches; and
[0329] (H) The process of grinding the surface of the conductor layer.
[0330] In the second embodiment, since the first plasma mask remains directly, chemical damage to the insulating material layer caused by stripping fluid or similar substances used during mask pattern removal can be suppressed. As a result, the insulating material layer exhibits excellent insulation and electrical properties, improving insulation performance after the HAST test. In particular, cured thermosetting materials tend to have superior insulation and electrical properties compared to cured photosensitive materials. Therefore, the combination of an insulating material layer formed from a cured thermosetting material and a first plasma mask formed from a cured photosensitive material can efficiently improve insulation and electrical properties. Furthermore, since a photosensitive material layer is formed on the insulating material layer, mask pattern alignment is easier, enabling the formation of small-diameter vias or trenches.
[0331] <Process (A)>
[0332] Step (A) is the same as step (1) in the first embodiment. The first photosensitive material is the same as the photosensitive material in the first embodiment.
[0333] <Process (B)>
[0334] In process (B), such as Figure 15 As shown in the example, the first photosensitive material layer 22 is irradiated with active energy rays for exposure and development to form a first plasma mask with an opening 212. Details regarding the exposure are available through... Figure 15 A photomask (not shown) is used to irradiate the surface of the first photosensitive material layer 22 with active energy rays, causing the first photosensitive material layer 22 to solidify.
[0335] The exposure and development methods for the first photosensitive material layer are the same as those in step (B) of the first embodiment. Furthermore, the thickness of the first plasma mask is the same as that of the plasma mask in step (B) of the first embodiment.
[0336] When the thickness of the first plasma mask after process (B) is set to T1A (μm) and the thickness of the insulating material layer after process (B) is set to T2A (μm), from the viewpoint of significantly obtaining the effect of the present invention, it is preferable to satisfy the relationship T1A>T2A.
[0337] <Process (C)>
[0338] In process (C), such as Figure 16 As shown in the example, plasma irradiation is performed on the insulating material layer 11 through the first plasma mask 24, forming either or both of a through-hole (not shown) and a trench 31 in the insulating material layer 11 at the opening 212 of the first plasma mask 24, and simultaneously etching is performed on the first plasma mask 24 to reduce its thickness. Step (C) can be performed by the same method as step (3) of the first embodiment.
[0339] <Process (D)>
[0340] In process (D), such as Figure 17 As shown in the example, either or both of coating and pasting of the second photosensitive material are performed to cover the surface and opening 212 of the first plasma mask 24, forming a second photosensitive material layer 23. The coating and pasting of the second photosensitive material is the same as step (1) in the first embodiment. The second photosensitive material may be the same as or different from the first photosensitive material.
[0341] <Process (E)>
[0342] In process (E), such as Figure 18 As shown in the example, the second photosensitive material layer 23 is irradiated with active energy rays for exposure and development to form a second plasma mask 25 having an opening 212 and a predetermined pattern. Details regarding the exposure are available through... Figure 18 An unillustrated photomask is used to irradiate the surface of the second photosensitive material layer with active energy rays, causing the second photosensitive material layer to solidify.
[0343] The exposure and development methods for the second photosensitive material layer are the same as those in step (B) of the first embodiment. Furthermore, the thickness of the second plasma mask is the same as that of the plasma mask in step (B) of the first embodiment.
[0344] <Process (F)>
[0345] In process (F), such as Figure 19As shown in one example, the first plasma mask 24 and the insulating material layer 11 are irradiated with plasma through a second plasma mask, forming either or both of vias (not shown) and trenches 31 in the insulating material layer 11. In this process, the first plasma mask 24 can be etched simultaneously to further reduce its thickness. In step (F), the second plasma mask may be completely removed by plasma etching, or it may remain.
[0346] Regarding plasma treatment, it is the same as the plasma treatment in step (3) of the first embodiment.
[0347] Furthermore, when the thickness of the plasma mask before plasma irradiation is set to 1, from the viewpoint of significantly obtaining the effects of the present invention, the thickness of the first plasma mask after process (F) is preferably 0.01 or more, more preferably 0.05 or more, further preferably 0.1 or more, or 0.15 or more. Preferably 0.7 or less, more preferably 0.6 or less, and further preferably 0.5 or less. It should be noted that conventional wiring board manufacturing methods remove or peel off the mask after forming through-holes or trenches; therefore, when the thickness of the mask before plasma treatment is set to 1, the thickness of the mask after plasma treatment is at most 0.05.
[0348] The thickness of the first plasma mask after process (F) is the same as or the thickness of the subtractive plasma mask after process (3) of the first embodiment.
[0349] <Process (G)>
[0350] In process (G), such as Figure 20 As shown in the example, a conductor layer 40 is formed on the surface of the first plasma mask 24 and either or both of the vias and trenches 31. The formation of the conductor layer is the same as that in step (4) of the first embodiment. Step (G) may include: (G-1) forming a plating seed layer 41 on the surface of the first plasma mask 24 and either or both of the vias (not shown) and trenches 31. The plating seed layer is the same as that in step (4) of the first embodiment. Alternatively, a barrier metal layer may be formed instead of the plating seed layer.
[0351] After forming the plating seed layer, the process may further include: (G-2) performing electroplating on the plating seed layer 41, and filling either or both of the through holes and trenches by electroplating to form a hole-filling process. Specifically, an electroplating layer 42 is formed on the exposed plating seed layer 41 by electroplating. Regarding either or both of the through holes and trenches, an electroplating layer 42 is formed on the exposed plating seed layer 41 by electroplating, and the through holes and trenches are filled by electroplating to form a hole-filling process. The electroplating process is the same as the formation of the electroplating layer in step (4) of the first embodiment.
[0352] <Process (H)>
[0353] In process (H), the surface of the conductor layer is ground, i.e., as shown in the image. Figure 21 As shown in the example, the surface of the conductor layer 40 is polished to expose the first plasma mask 24. As a polishing method, a method capable of polishing the surface of the conductor layer can be used. Examples of such polishing methods include CMP (chemical mechanical polishing), polishing, and belt polishing. CMP is preferred.
[0354] After process (H), a barrier metal layer may be formed on the surface of the conductor layer as needed. Furthermore, during the fabrication of the wiring board, processes (A) through (H) may be repeated as needed to form a multilayer wiring board.
[0355] The preferred area for the wiring board is 2500 mm². 2 The above, preferably 3000mm 2 The above is further preferred to be 3500mm. 2 That's all. There's no specific upper limit; it can be set to 10000mm. 2 The following, etc.
[0356] The wiring board obtained by the manufacturing method of the present invention can be a multilayer wiring substrate with multiple conductor layers stacked on top of each other. Preferably, there are three or more conductor layers in the multilayer wiring substrate.
[0357] [Semiconductor Devices]
[0358] The semiconductor device of the present invention comprises a wiring board obtained by the manufacturing method of the present invention. Examples of semiconductor devices include various semiconductor devices used in electrical products (e.g., computers, mobile phones, digital cameras, and televisions) and vehicles (e.g., motorcycles, automobiles, trams, ships, and airplanes).
[0359] The semiconductor device of the present invention can have a fan-out structure or a chiplet structure. Furthermore, the semiconductor device of the present invention has semiconductor chips on a wiring board obtained by the manufacturing method of the present invention, which are preferably a hybrid system of at least logic chips and memory chips.
[0360] Example
[0361] The present invention will now be described in detail with reference to embodiments. However, the present invention is not limited to these embodiments. In the following description, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "% by mass," respectively. Furthermore, unless otherwise specified, the operations described below are performed in an environment of normal temperature and pressure.
[0362] Inorganic filler materials 1 and 2 are shown below.
[0363] Inorganic filler material 1: Spherical silica (DENKA's "UFP-30", average particle size: 0.078 μm, specific surface area: 30.7 m²) 2 / g) is prepared by surface treatment with N-phenyl-3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Industry Co., Ltd., KBM573).
[0364] Inorganic filler material 2: Spherical silica (ADMATECHS "SO-C2", average particle size: 0.5 μm, specific surface area: 5.8 m²) 2 / g) is prepared by surface treatment with N-phenyl-8-aminooctyltrimethoxysilane (manufactured by Shin-Etsu Chemical Industry Co., Ltd., KBM6803).
[0365] <Preparation of Thermosetting Material 1>
[0366] Six parts of xylenol-type epoxy resin (Mitsubishi Chemical Corporation's "YX4000HK", epoxy equivalent approximately 185 g / eq.), five parts of naphthalene-type epoxy resin (Nippon Steel & Sumitomo Chemical Corporation's "ESN475V", epoxy equivalent approximately 332 g / eq.), fifteen parts of bisphenol AF-type epoxy resin (Mitsubishi Chemical Corporation's "YL7760", epoxy equivalent approximately 238 g / eq.), and one part of naphthalene ether-type epoxy resin (DIC Corporation's "HP6000L"). Two parts of an epoxy resin (approximately 213 g / eq.), two parts of a cyclohexane-type epoxy resin (Mitsubishi Chemical Corporation's "ZX1658GS", approximately 135 g / eq.), two parts of a phenoxy resin (Mitsubishi Chemical Corporation's "YX7800BH30"), and 20 parts of a 1:1 solution of cyclohexanone and methyl ethyl ketone (MEK) with a solid content of 30% by mass (Mw = 20000) were dissolved in a mixed solvent of 20 parts naphtha and 10 parts cyclohexanone while stirring and heating. After cooling to room temperature, 20 parts of a prepolymer ("BA230S" manufactured by Arxada Corporation, with a cyanate equivalent of 232 g / eq.) formed by triazinization of part or all of bisphenol A dicyanate, and 0.05 parts of an amine curing accelerator (4-dimethylaminopyridine (DMAP)) were mixed in and uniformly dispersed using a high-speed rotary stirrer and then filtered using a cartridge filter ("SHP020" manufactured by ROKITECHNO Corporation) to prepare thermosetting material 1.
[0367] <Preparation of Thermosetting Material 2>
[0368] Six parts of xylenol-type epoxy resin (Mitsubishi Chemical Corporation's "YX4000HK", epoxy equivalent approximately 185 g / eq.), five parts of naphthalene-type epoxy resin (Nippon Steel & Sumitomo Chemical Corporation's "ESN475V", epoxy equivalent approximately 332 g / eq.), fifteen parts of bisphenol AF-type epoxy resin (Mitsubishi Chemical Corporation's "YL7760", epoxy equivalent approximately 238 g / eq.), and one part of naphthalene ether-type epoxy resin (DIC Corporation's "HP6000L"). Two parts of an epoxy resin (approximately 213 g / eq.), two parts of a cyclohexane-type epoxy resin (Mitsubishi Chemical Corporation's "ZX1658GS", approximately 135 g / eq.), two parts of a phenoxy resin (Mitsubishi Chemical Corporation's "YL7500BH30"), and two parts of a 1:1 solution of cyclohexanone and methyl ethyl ketone (MEK) with a solid content of 30% by mass (Mw = 44000) were dissolved in a mixed solvent of 20 parts naphtha and 10 parts cyclohexanone while stirring and heating. After cooling to room temperature, 4 parts of a cresol phenolic varnish curing agent containing a triazine skeleton (DIC's "LA-3018-50P", hydroxyl equivalent of approximately 151 g / eq., 50% solids in a 2-methoxypropanol solution), 6 parts of an active ester curing agent (DIC's "HP-B-8151-62T", active group equivalent of 238 g / eq., 62% solids in a toluene solution), 130 parts of inorganic filler, and 0.05 parts of an amine curing accelerator (4-dimethylaminopyridine (DMAP)) were mixed in. After being evenly dispersed using a high-speed rotary stirrer, the mixture was filtered using a cartridge filter (ROKITECHNO's "SHP020") to prepare thermosetting material 2.
[0369] <Preparation of Thermosetting Material 3>
[0370] Six parts of xylenol-type epoxy resin (Mitsubishi Chemical Corporation's "YX4000HK", epoxy equivalent approximately 185 g / eq.), five parts of naphthalene-type epoxy resin (Nippon Steel & Sumitomo Chemical Corporation's "ESN475V", epoxy equivalent approximately 332 g / eq.), fifteen parts of bisphenol AF-type epoxy resin (Mitsubishi Chemical Corporation's "YL7760", epoxy equivalent approximately 238 g / eq.), and one part of naphthalene ether-type epoxy resin (DIC Corporation's "HP60"). 2 parts of cyclohexane-type epoxy resin (Mitsubishi Chemical Corporation's "ZX1658GS", epoxy equivalent approximately 213), 2 parts of phenoxy resin (Mitsubishi Chemical Corporation's "YL7500BH30", a 1:1 solution of cyclohexanone and methyl ethyl ketone (MEK) with a solid content of 30% by mass, Mw = 44000) were dissolved in a mixed solvent of 20 parts naphtha and 10 parts cyclohexanone while stirring and heating. After cooling to room temperature, 4 parts of a cresol phenolic varnish curing agent containing a triazine skeleton (DIC's "LA-3018-50P", hydroxyl equivalent of approximately 151 g / eq., 50% solids in a 2-methoxypropanol solution), 6 parts of an active ester curing agent (DIC's "HP-B-8151-62T", active group equivalent of 238 g / eq., 62% solids in a toluene solution), 160 parts of inorganic filler, and 0.05 parts of an amine curing accelerator (4-dimethylaminopyridine (DMAP)) were mixed in. After being evenly dispersed using a high-speed rotary stirrer, the mixture was filtered using a cartridge filter (ROKITECHNO's "SHP020") to prepare thermosetting material 3.
[0371] <Preparation of Thermosetting Material 4>
[0372] Six parts of xylenol-type epoxy resin (Mitsubishi Chemical Corporation's "YX4000HK", epoxy equivalent approximately 185 g / eq.), five parts of naphthalene-type epoxy resin (Nippon Steel & Sumitomo Chemical Corporation's "ESN475V", epoxy equivalent approximately 332 g / eq.), fifteen parts of bisphenol AF-type epoxy resin (Mitsubishi Chemical Corporation's "YL7760", epoxy equivalent approximately 238 g / eq.), and one part of naphthalene ether-type epoxy resin (DIC Corporation's "HP60"). 2 parts of cyclohexane-type epoxy resin (Mitsubishi Chemical Corporation's "ZX1658GS", epoxy equivalent approximately 213), 2 parts of phenoxy resin (Mitsubishi Chemical Corporation's "YL7500BH30", a 1:1 solution of cyclohexanone and methyl ethyl ketone (MEK) with a solid content of 30% by mass, Mw = 44000) were dissolved in a mixed solvent of 20 parts naphtha and 10 parts cyclohexanone while stirring and heating. After cooling to room temperature, 4 parts of a cresol phenolic varnish curing agent containing a triazine skeleton (DIC's "LA-3018-50P", hydroxyl equivalent of approximately 151 g / eq., 50% solids in a 2-methoxypropanol solution), 6 parts of an active ester curing agent (DIC's "HP-B-8151-62T", active group equivalent of 238 g / eq., 62% solids in a toluene solution), solvent IP150 (Idemitsu Kosan), 2150 parts of inorganic filler, and 0.05 parts of an amine curing accelerator (4-dimethylaminopyridine (DMAP)) were mixed in. After being evenly dispersed using a high-speed rotary stirrer, the mixture was filtered using a cartridge filter (ROKITECHNO's "SHP050") to prepare thermosetting material 4.
[0373] The components used to prepare thermosetting materials 1 to 4 and their mixing amounts are shown in the table below.
[0374] [Table 1]
[0375] (surface)
[0376]
[0377] *In the table, the content of curing agent indicates the content of curing agent when the resin component in the thermosetting material is set to 100% by mass. The content of cyanate ester resin, reactive ester resin, phenol resin and inorganic filler material indicates the content when the non-volatile component in the thermosetting material is set to 100% by mass.
[0378] <Preparation of Thermosetting Resin Sheet 1>
[0379] As a support, a PET film (Toray Industries' "Lumirror R80", 38 μm thick, softening point 130°C, "release PET") that has undergone release treatment using an alkyd resin-based release agent (LINTEC's "AL-5") is prepared. Using a die coater, thermosetting material 1 is uniformly coated onto the release agent of the support with a dried thermosetting material layer thickness of 5 μm, and dried at 70°C to 95°C for 2 minutes, thereby obtaining a thermosetting material layer on the release PET. Next, a polypropylene film (OJI F-TEC's "ALPHAN MA-411", 15 μm thick), serving as a protective film, is laminated onto the surface of the resin sheet that is not bonded to the support, in a manner that bonds to the thermosetting material layer. This yields a thermosetting resin sheet 1 for forming an insulating material layer, consisting of the release PET (support), the thermosetting material layer, and the protective film in that order.
[0380] <Preparation of Thermosetting Resin Sheet 2>
[0381] In the fabrication of thermosetting resin sheet 1, thermosetting material 1 is changed to thermosetting material 2. Except as described above, thermosetting resin sheet 2 is fabricated using the same procedure as thermosetting resin sheet 1.
[0382] <Preparation of Thermosetting Resin Sheet 3>
[0383] In the fabrication of thermosetting resin sheet 1, thermosetting material 1 is replaced with thermosetting material 3. Except as described above, thermosetting resin sheet 3 is fabricated using the same procedure as thermosetting resin sheet 1.
[0384] <Preparation of Thermosetting Resin Sheet 4>
[0385] In the fabrication of thermosetting resin sheet 1, thermosetting material 1 is replaced with thermosetting material 4. Except as described above, thermosetting resin sheet 4 is fabricated using the same procedure as thermosetting resin sheet 1.
[0386] <Preparation of Photosensitive Material 1>
[0387] 10 parts by mass of alkali-soluble resin (“TR4020G”, manufactured by Asahi Organic Materials Co., Ltd.), 5 parts by mass of alkali-soluble resin (“MEHC-7851SS”, manufactured by Meiwa Chemical Co., Ltd.), 5 parts by mass of alkali-soluble resin (“BisE”, manufactured by Honshu Chemical Co., Ltd.), 5 parts by mass of compound containing at least two alkoxymethyl groups in the molecule (“MW-390”, manufactured by Sanwa Chemical Co., Ltd.), 0.05 parts by mass of photoacid generator (“MP-triazine”, manufactured by Sanwa Chemical Co., Ltd.), 2 parts by mass of organic filler material (“MM-101SM”, manufactured by Negami Kogyo Co., Ltd.), and 12 parts by mass of MEK (manufactured by Junsei Chemical Co., Ltd.) were mixed to obtain negative photosensitive material 1.
[0388] <Preparation of Photosensitive Material 2>
[0389] (Synthesis of polybenzoxazole precursor resin)
[0390] 443.2 g (0.90 mol) of a dicarboxylic acid derivative obtained by reacting 1 mole of diphenyl ether-4,4'-dicarboxylic acid with 2 moles of 1-hydroxybenzotriazole and 366.3 g (1.00 mol) of hexafluoro-2,2-bis(3-amino-4-hydroxyphenyl)propane were added to a four-necked separable flask equipped with a thermometer, stirrer, feed inlet, and dry nitrogen inlet tube. 3000 g of N-methyl-2-pyrrolidone was added to dissolve the derivative. The reaction was then carried out in an oil bath at 75°C for 16 hours.
[0391] Next, 32.8 g (0.20 mol) of 5-norbornene-2,3-dicarboxylic anhydride dissolved in 100 parts by mass of N-methyl-2-pyrrolidone was added, and the mixture was stirred for another 3 hours to stop the reaction. After filtering the reaction mixture, it was added to a solution of water / isopropanol = 3 / 1, the precipitate was filtered off, and the mixture was thoroughly washed with water and dried under vacuum to obtain the target polybenzoxazole precursor resin (A-1), which is a polybenzoxazole precursor resin randomly copolymerized from general formulas (5-4) and (5-5) with a number average molecular weight of 12000.
[0392] (Synthesis of photosensitive diazonoquinone compounds)
[0393] 12.74 g (0.030 mol) of the phenol compound shown in formula (1) and 7.59 g (0.075 mol) of triethylamine were added to a four-necked separable flask equipped with a thermometer, stirrer, raw material inlet, and dry nitrogen inlet tube, and 103 g of acetone was added to dissolve them. After cooling the reaction solution to below 10°C, 20.15 g (0.075 mol) of 1,2-naphthoquinone-2-diazo-5-sulfonyl chloride and 100 g of acetone were slowly added dropwise without reaching above 10°C. Then, the mixture was stirred at below 10°C for 5 minutes and then stirred at room temperature for 5 hours to complete the reaction. After filtering the reaction mixture, the reaction mixture was added to a solution of water / methanol = 3 / 1 (volume ratio), the precipitate was filtered off, and after being thoroughly washed with water, it was dried under vacuum to obtain the photosensitive diazonoquinone compound shown in formula (2).
[0394] [Chemistry 1]
[0395]
[0396] [Chemistry 2]
[0397]
[0398] In formula (2), Q represents a hydrogen atom or a group shown in formula (3), and 83% of Q is a group shown in formula (3).
[0399] In equation (3), * represents a connection key.
[0400] (Preparation of photosensitive material 2)
[0401] 100g of the synthesized polybenzoxazole precursor resin (A-1), 19g of the photosensitive diazoquinone compound shown in formula (2), 4g of the hindered phenolic antioxidant shown in formula (5), 10g of the phenol compound shown in formula (4), and 8g of 3-methacryloyloxypropyltrimethoxysilane were dissolved in 200g of γ-butyrolactone and then filtered through a 0.2μm Teflon (registered trademark) filter to obtain positive photosensitive material 2.
[0402] <Preparation of Photosensitive Material 3>
[0403] (Synthesis of Polymer A)
[0404] 155.1 g of 4,4'-oxophthalic dianhydride (ODPA) was added to a 2 L separable flask, along with 131.2 g of 2-hydroxyethyl methacrylate (HEMA) and 400 mL of γ-butyrolactone. The mixture was stirred at room temperature, and 81.5 g of pyridine was added while stirring to obtain the reaction mixture. After the exothermic reaction was completed, the mixture was cooled to room temperature and allowed to stand for 16 hours.
[0405] Next, under ice-cold conditions, a solution of 206.3 g of dicyclohexylcarbodiimide (DCC) dissolved in 180 mL of γ-butyrolactone was added to the reaction mixture over 40 minutes with stirring. Then, a mixture of 45.1 g of 4,4'-diaminodiphenyl ether (DADPE) suspended in 350 mL of γ-butyrolactone was added over 60 minutes with stirring. After stirring at room temperature for 2 hours, 30 mL of ethanol was added and stirring for 1 hour, followed by the addition of 400 mL of γ-butyrolactone. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.
[0406] The resulting reaction solution was added to 3 L of ethanol, generating a precipitate containing the crude polymer. The crude polymer was filtered and dissolved in 1.5 L of γ-butyrolactone to obtain a crude polymer solution. The crude polymer solution was added dropwise to 28 L of water to precipitate the polymer. The precipitate was filtered and then vacuum dried to obtain a powdered polymer (polymer A).
[0407] (Preparation of photosensitive material 3)
[0408] 100g of polymer A was dissolved together with 4g of photopolymerization initiator (1-[4-(phenylthio)phenyl]-3-cyclopentylprop-1,2-dione-2-(o-benzoyl oxime)) and 4g of tetraethylene glycol dimethacrylate in a mixed solvent containing 80g of N-methyl-2-pyrrolidone and 20g of ethyl lactate. The viscosity of the resulting solution was adjusted to approximately 35 poise by further adding a small amount of the aforementioned mixed solvent, thus obtaining negative photosensitive material 3.
[0409] <Preparation of Photosensitive Material 4>
[0410] (Synthesis of p-hydroxystyrene / styrene copolymer A1)
[0411] 100 parts by mass of p-tert-butoxystyrene and styrene were prepared in a molar ratio of 85:15 and dissolved in 150 parts by mass of propylene glycol monomethyl ether. The reaction was carried out under a nitrogen atmosphere at 70°C, with 4 parts by mass of azobisisobutyronitrile (AIBN) stirred at approximately 160 rpm for 10 hours. Subsequently, sulfuric acid was added to the reaction solution, and the reaction temperature was maintained at 90°C for 10 hours to deprotect the p-tert-butoxystyrene and convert it to hydroxystyrene. Ethyl acetate was added to the resulting copolymer, and the mixture was washed with water five times. The ethyl acetate phase was separated, and the solvent was removed to obtain p-hydroxystyrene / styrene copolymer A1 (hereinafter, p-hydroxystyrene / styrene copolymer A1 is sometimes referred to as "A1").
[0412] (Preparation of photoacid generator and crosslinking agent)
[0413] As a photoacid generator, 1-naphthoquinone-2-diazo-5-sulfonate of 1,1-bis(4-hydroxyphenyl)-1-[4-{1-(4-hydroxyphenyl)-1-methylethyl}phenyl]ethane (esterification rate of approximately 90%, manufactured by AZ ELECTRONIC MATERIALS, "TPPA528") (hereinafter, this photoacid generator is sometimes referred to as "B1").
[0414] As a crosslinking agent, prepare hexa(methoxymethyl)melamine (manufactured by Sanwa Chemical Co., Ltd., "NIKALAC MW-30HM" (hereinafter, this crosslinking agent is sometimes referred to as "C1").
[0415] (Synthesis of acrylic resin D1)
[0416] Weigh 55 g of ethyl lactate into a 100 ml three-necked flask equipped with a stirrer, nitrogen inlet tube, and thermometer. Add separately weighed polymerizable monomers: 34.7 g of n-butyl acrylate (BA), 2.2 g of lauryl acrylate (LA), 3.9 g of acrylic acid (AA), 2.6 g of hydroxybutyl acrylate (HBA), 1.7 g of 1,2,2,6,6-pentamethylpiperidin-4-yl methacrylate (RESONAC, “FA-711MM”), and 0.29 g of azobisisobutyronitrile (AIBN). Stir at room temperature. The mixture was stirred at approximately 160 rpm while nitrogen gas was passed through at a flow rate of 400 ml / min for 30 minutes to remove dissolved oxygen. Afterward, the nitrogen flow was stopped, the flask was sealed, and the temperature was raised to 65°C over approximately 25 minutes using a constant-temperature water bath. This temperature was maintained for 10 hours to carry out the polymerization reaction, yielding acrylic resin D1 (hereinafter sometimes referred to as "D1"). The polymerization rate at this point was 99%. Furthermore, the weight-average molecular weight of D1 was approximately 22,000. It should be noted that the molar ratios of the polymerizable monomers in D1 are as follows.
[0417] BA / LA / AA / HBA / FA711MM=75.5 / 2.5 / 15 / 5 / 2(mol%)
[0418] (Preparation of photosensitive material 4)
[0419] A 50% methanol solution of 180 parts A, 120 parts B, 15 parts C, 120 parts D, 120 parts ethyl lactate as solvent, and 2 parts ureapropyltriethoxysilane as coupling agent was prepared and filtered under pressure using a Teflon (registered trademark) filter with 3 μm pores to prepare photosensitive material 4.
[0420] (Preparation of photosensitive material 5)
[0421] As the photosensitive material 5, epoxy resin photosensitive material SU-83010 (manufactured by Nippon Kayaku Co., Ltd.) is used.
[0422] <Preparation of Photosensitive Resin Sheet A>
[0423] As a support, a PET film (Toray Industries' "Lumirror T60", 38 μm thick) was prepared. Using a die-coating machine, photosensitive material 1 was uniformly coated onto the PET film to a thickness of 10 μm after drying. The film was then dried at 80°C to 110°C for 6 minutes, thereby obtaining a photosensitive resin sheet A with a photosensitive material layer on the demolded PET.
[0424] [Example 1]
[0425] <Evaluation of substrate fabrication>
[0426] (1) Preparation of silicon wafers
[0427] As a substrate, a silicon wafer with a copper layer stacked on one side (copper foil thickness of 1μm, substrate thickness of 0.8mm, 8-inch size) was placed in an oven at 130°C and dried for 30 minutes.
[0428] (2) Lamination of thermosetting resin sheets
[0429] The protective film of thermosetting resin sheet 1 is peeled off, and laminated onto one side of the wafer using an intermittent vacuum pressure laminator (NIKKO MATERIALS, two-stage laminator, CVP700), with the thermosetting material layer in contact with the silicon wafer. The lamination is performed as follows: depressurization for 30 seconds to bring the pressure below 13 hPa, followed by pressing for 45 seconds at 130°C and 0.74 MPa. Then, thermal pressurization is applied for 75 seconds at 120°C and 0.5 MPa.
[0430] (3) Thermosetting of thermosetting material layer
[0431] A silicon wafer with a thermosetting resin sheet 1 laminated on it is placed in an oven at 100°C and the thermosetting material layer is heat-cured for 30 minutes. Then, it is transferred to an oven at 180°C and the thermosetting material layer is heat-cured for 30 minutes to form an insulating material layer. The support is then peeled off. As a result, a substrate A with an insulating material layer having a thickness of 5 μm is obtained.
[0432] (4) Lamination of photosensitive resin sheet A
[0433] A photosensitive resin sheet A is laminated onto the insulating material layer of substrate A. Specifically, lamination is performed using an intermittent vacuum pressure laminator (NIKKO MATERIALS, two-stage laminator, CVP700) with substrate A in contact with the photosensitive material layer of photosensitive resin sheet A. The lamination is performed by depressurizing for 30 seconds to bring the pressure down to below 13 hPa, then pressing it for 45 seconds at 80°C and 0.74 MPa. Next, hot pressurization is performed for 75 seconds at 80°C and 0.5 MPa.
[0434] (5) Patterning of photosensitive material layers
[0435] After laminating photosensitive resin film A, substrate A was baked at 80°C for 30 seconds and exposed for 1800 msec using a Ushio UX-2240 electric motor. After exposure, substrate A was baked at 75°C for 180 seconds and then developed using a 2.38% TMAH solution under paddle conditions of 30 seconds × 2 cycles. The developed pattern was then descaled using a SAMCO plasma apparatus (O2 flow rate: 50 sccm, RF power: 500 W, process pressure: 12 Pa, processing time: 1 minute). Subsequently, it was heated to 5000 mJ / cm². 2 After exposure and baking, a final curing process is performed to obtain a product with... Plasma mask with mask pattern. Post-curing is performed by heating at 50°C for 30 minutes, then placing for 30 minutes; heating at 100°C for 30 minutes, then placing for 30 minutes; heating at 190°C for 60 minutes, then cooling to 50°C for more than 30 minutes.
[0436] (6) Formation of vias and plasma dry etching of plasma mask
[0437] Using a plasma dry etching apparatus (Oxford Instruments PlasmaPro100), a CF4 / O2 mixing ratio of 80:20 (sccm), a vacuum level of 50 mTorr, RF power of 120 W, and ICP power of 100 W, plasma treatment was performed on the plasma mask obtained in step (5) to form vias in the insulating material layer. This plasma treatment continued until the plasma mask was not completely removed and remained on the insulating material layer.
[0438] (7) Determination of arithmetic mean roughness (Ra)
[0439] The arithmetic mean roughness (Ra) of the plasma mask surface after through-hole formation was measured using a non-contact surface roughness meter (WYKO NT3300, Veeco Instruments). The measurement was performed in VSI mode with a 50x lens and a measurement range of 121 μm × 92 μm.
[0440] (8) Determination of the wall roughness (Sa) of the through hole
[0441] After forming through-holes in the insulating material layer, the mask pattern is ground to form a cross-section, and the wall roughness of the through-holes is measured. A laser microscope (KEYENCE, "VK-X3000") is used to measure the wall roughness of the through-holes.
[0442] (9) Determination of pore cone angle and pore expansion rate
[0443] The cross-sections before and after the formation of through-holes were observed using a FIB-SEM (Ethos NX5000) manufactured by Hitachi High-Tech Corporation, and the hole taper angle and hole expansion rate were measured.
[0444] (10) Formation of the conductor layer
[0445] Using a sputtering device (“E-400S” manufactured by CANON ANELVA Corporation), the surface of the plasma mask after the formation of through-holes was sputtered to form a titanium layer with a thickness of 10 nm, and then a copper layer with a thickness of 100 nm was formed. Thereafter, annealing treatment was performed by heating at 150 °C for 30 minutes. Then, according to the semi-additive method, a resist layer was formed, and after forming a comb pattern with L / S = 1 / 1 μm (line width 1 mm) by exposure / development, copper sulfate electroplating was performed to form a conductor layer with a thickness of 2 μm. After forming the conductor pattern, annealing treatment was performed by heating at 200 °C for 60 minutes. The obtained substrate was designated as “substrate B”.
[0446] <Evaluation of micro-wiring (Appearance evaluation)>
[0447] The comb wiring of substrate B was confirmed using a microscope (“VHX-7000” manufactured by KEYENCE Corporation) and evaluated according to the following criteria. Here, “wiring breakaway” means that the conductor layer was not formed at the desired position and the comb pattern of the conductor layer was interrupted halfway.
[0448] 〇: No wiring breakaway was observed in the comb pattern.
[0449] ×: Wiring breakaway was observed in the comb pattern.
[0450] <Evaluation of insulation after HAST test>
[0451] The comb pattern of substrate B was filled with the thermosetting material layer of the thermosetting resin sheet 1 and cured. Specifically, the protective film of the thermosetting resin sheet was peeled off, and a batch-type vacuum pressure laminator (two-stage laminator, CVP700 manufactured by NIKKO MATERIALS Company) was used to laminate in such a way that the thermosetting material layer was in contact with the conductor layer of substrate B. The lamination was carried out by the following operations: reducing the pressure for 30 seconds to make the air pressure 13 hPa or less, and crimping it for 45 seconds under the conditions of 130 °C and a pressure of 0.74 MPa. Then, thermal pressing was carried out for 75 seconds under the conditions of 120 °C and a pressure of 0.5 MPa. The laminated substrate B was heated at 180 °C for 90 minutes to cure the thermosetting material layer, exposing the electrode part connected to the comb pattern, applying a voltage of 1.0 V, and performing a test at 130 °C, 85 RH%, and 200 h, and the insulation was confirmed according to the following criteria.
[0452] 〇: Resistance value exceeds 10 6 Ω.
[0453] ×: Resistance value is 10 6 Below Ω.
[0454] <Determination of Overall Linear Thermal Expansion Coefficient (Overall CTE)>
[0455] Use the following formula to calculate the overall linear thermal expansion coefficient.
[0456] Overall linear thermal expansion coefficient = linear thermal expansion coefficient of the subtractive plasma mask × (thickness of the subtractive plasma mask / thickness of the subtractive plasma mask + thickness of the insulating material layer) + linear thermal expansion coefficient of the insulating material layer × (thickness of the insulating material layer / thickness of the subtractive plasma mask + thickness of the insulating material layer)
[0457] [Example 2]
[0458] In Example 1, thermosetting resin sheet 1 was replaced with thermosetting resin sheet 2. Except as described above, substrate A was fabricated and evaluated in the same manner as in Example 1.
[0459] [Example 3]
[0460] In Example 1, thermosetting resin sheet 1 was replaced with thermosetting resin sheet 3. Except as described above, substrate A was fabricated and evaluated in the same manner as in Example 1.
[0461] [Example 4]
[0462] In Example 1, thermosetting resin sheet 1 was replaced with thermosetting resin sheet 4. Except as described above, substrate A was fabricated and evaluated in the same manner as in Example 1.
[0463] [Example 5]
[0464] In Example 2, the lamination of (4) photosensitive resin sheet A was changed to the formation of a coating of photosensitive material 2 as described in (4-1), and the patterning of (5) photosensitive material layer was changed to the patterning of the coating of photosensitive material 2 as described in (5-1). Except for the above, the same procedure as in Example 2 was followed to fabricate substrate A and evaluate it.
[0465] (4-1) Formation of the coating of photosensitive material 2
[0466] Using a spin coater, photosensitive material 2 is coated onto a silicon wafer, and then pre-baked at 120°C for 4 minutes using a heating plate to obtain a coating film with a thickness of approximately 10 μm.
[0467] (5-1) Patterning of the coating of photosensitive material 2
[0468] Using an i-ray stepper lithography machine (Nikon's "4425i"), at an exposure dose of 280 mJ / cm², 2 Under these conditions, the coating was exposed. Then, using a 2.38% tetramethylammonium hydroxide aqueous solution, the development time was adjusted so that the thickness difference between the pre-baked and developed unexposed areas was 1 μm, and paddle development was performed. Subsequently, a pattern was formed by rinsing with pure water for 10 seconds to obtain the plasma mask.
[0469] [Example 6]
[0470] In Example 2, the lamination of (4) photosensitive resin sheet A was changed to the formation of a coating of photosensitive material 3 as described in (4-2), and the patterning of (5) photosensitive material layer was changed to the patterning of the coating of photosensitive material 3 as described in (5-2). Except for the above, the same procedure as in Example 2 was followed to fabricate substrate A and evaluate it.
[0471] (4-2) Formation of the coating film of photosensitive material 3
[0472] Using a spin coater, photosensitive material 3 is coated onto a silicon wafer and then dried to obtain a coating film with a thickness of 10 μm.
[0473] (5-2) Patterning of the coating of photosensitive material 3
[0474] Using a GHI stepper lithography machine (Prisma-GHI, manufactured by UltraTech), at an exposure dose of 500 mJ / cm² 2 Under the specified conditions, the coating was exposed. Next, the coating was spray-developed using cyclopentanone and a developer (Dai Nippon Screen Manufacturing Co., Ltd., "D-SPIN636"). Unexposed areas were then removed by washing with propylene glycol methyl ether acetate, thereby forming a pattern on the coating. The pattern was cured in a temperature-programmed curing oven (Koyo Lindberg Co., Ltd., "VF-2000") at 200°C for 2 hours under a nitrogen atmosphere, resulting in a cured pattern (plasma mask) with a thickness of approximately 9 μm.
[0475] [Example 7]
[0476] In Example 2, the lamination of (4) photosensitive resin sheet A was changed to the formation of a coating of photosensitive material 4 as described in (4-3), and the patterning of (5) photosensitive material layer was changed to the patterning of the coating of photosensitive material 4 as described in (5-3). Except for the above, the same procedure as in Example 2 was followed to fabricate substrate A and evaluate it.
[0477] (4-3) Formation of the coating of photosensitive material 4
[0478] Photosensitive material 4 was spin-coated onto a silicon wafer substrate and heated at 120°C for 4 minutes to form a coating film with a thickness of 10 μm.
[0479] (5-3) Patterning of the coating of photosensitive material 4
[0480] An i-ray stepper lithography machine (Canon FPA-3000iW) was used to expose the coating using i-rays (365nm). The exposure was achieved at 460mJ / cm². 2 Exposure was performed using the specified exposure level. After exposure, development was performed using a 2.38% aqueous solution of tetramethylammonium hydroxide (TMAH). Subsequently, the pattern was heated for 2 hours in a vertical diffusion furnace (Koyo Thermo Systems, "μ-TF") under nitrogen atmosphere at a temperature of 200°C (heating time of 1.5 hours) to obtain the plasma mask.
[0481] [Example 8]
[0482] In Example 2, the lamination of (4) photosensitive resin sheet A was changed to the formation of a coating of photosensitive material 5 as described below (4-4), and the patterning of (5) photosensitive material layer was changed to the patterning of the coating of photosensitive material 5 as described in (5-4). Except for the above, the same procedure as in Example 2 was followed to fabricate substrate A and evaluate it.
[0483] (4-4) Formation of the coating of photosensitive material 5
[0484] Photosensitive material 5 was spin-coated onto a silicon wafer substrate and heated at 95°C for 10 minutes to form a coating film with a thickness of 10 μm.
[0485] (5-4) Patterning of the coating of photosensitive material 5
[0486] An i-ray stepper lithography machine (Canon FPA-3000iW) was used to expose the coating using i-rays (365nm). The exposure was performed at 200mJ / cm². 2 Exposure was performed using the specified exposure level. After exposure, the image was baked at 95°C for 5 minutes. Next, development was performed using a SU-8 Developer (manufactured by Nippon Kayaku Co., Ltd.). Subsequently, the pattern was heat-treated for 2 hours in a vertical diffusion furnace (manufactured by Koyo ThermoSystems, "μ-TF") at 200°C (heating time 1.5 hours) under nitrogen atmosphere to obtain the plasma mask.
[0487] [Comparative Example 1]
[0488] In Example 2, the following steps were changed: (3) thermosetting of the thermosetting material layer, (4) lamination of the photosensitive resin sheet A, and (5) patterning of the photosensitive material layer. Except for the above, the substrate B was fabricated and evaluated in the same manner as in Example 2.
[0489] After laminating the thermosetting resin sheet 2, the support is peeled off, the pressure is reduced for 30 seconds to bring the air pressure to below 13 hPa, and the copper foil (Mitsui Metals & Mining Co., Ltd., "MT-EX") is pressed onto the thermosetting material layer for 45 seconds at 130°C and 0.74 MPa. Then, it is heat-pressed for 75 seconds at 120°C and 0.5 MPa, thereby laminating the copper foil onto the thermosetting material layer.
[0490] After placing the silicon wafer with copper foil laminated on it into an oven at 100°C, the thermosetting material layer is heat-cured for 30 minutes. Then, it is transferred to an oven at 180°C and the thermosetting material layer is heat-cured for 30 minutes to form an insulating material layer.
[0491] After peeling off the carrier support of the copper foil, a photosensitive film (Showa Denko Materials Co., Ltd., "RY5115") was pasted onto it using a laminating apparatus (NIKKO MATERIALS, "V-160"). Exposure was performed using a Ushio Electric Machinery UX-2240 at 125 mJ. The photosensitive film was developed using Mitsubishi Gas Chemical Co., Ltd. EF-105A diluted 5 times with pure water to obtain... The mask pattern.
[0492] For this mask, the copper foil was dissolved using an adjusted etching solution (JCU, "SACII-710W3C", approximately 1020 mL of Millipore water, 36 g of CuSO4·5H2O, 80 mL of 75% H2SO4, 24 mL of SACII, and 260 mL of 35% H2O). Then, the mask pattern was removed using 180 mL of stripping solution (Mitsubishi Gas Chemical, "R-100S"), 97 mL of stripping solution (Mitsubishi Gas Chemical, "R-101"), and 923 mL of Millipore water, yielding the desired result. Cu mask pattern.
[0493] In Comparative Example 1, a Cu mask pattern was used to attempt to form vias and a conductor layer. However, due to the high surface roughness, it was difficult to etch when forming the plating seed layer. Therefore, it was impossible to form a conductor layer with a wiring pattern of L / S = 1 / 1 μm.
[0494] [Comparative Example 2]
[0495] In Example 2, the following steps were changed: (4) lamination of photosensitive resin sheet A, (5) patterning of photosensitive material layer and (6) formation of through hole. Except for the above, the substrate B was fabricated and evaluated in the same manner as in Example 2.
[0496] After curing the thermosetting material layer of the thermosetting resin sheet 2, a photosensitive film (Showa Denko Materials Co., Ltd., "RY5115") was pasted onto it using a laminating apparatus (NIKKOMATERIALS, "V-160"). Exposure was performed at 125 mJ using a Ushio Electric Machinery UX-2240. The photosensitive film was developed using Mitsubishi Gas Chemical Co., Ltd. EF-105A diluted 5 times with pure water to obtain... The mask pattern.
[0497] Plasma dry etching was performed on the mask pattern using an Oxford Instruments PlasmaPro100 apparatus with a CF4 / O2 mixing ratio of 80:20 (sccm), a vacuum level of 50 mTorr, RF power of 120 W, and ICP power of 100 W to form vias in the insulating material layer. Subsequently, a stripping solution (Mitsubishi Gas Chemical Co., Ltd., "R-100S") was used to strip the mask pattern. During the stripping process, chemical damage was observed at the points in the insulating material layer that came into contact with the stripping solution.
[0498] [Comparative Example 3]
[0499] In Example 2, the following steps were changed: (4) lamination of photosensitive resin sheet A, (5) patterning of photosensitive material layer and (6) formation of through hole. Except for the above, the substrate B was fabricated and evaluated in the same manner as in Example 2.
[0500] An opening was made in the insulating material layer of substrate A using a UV laser (LUK-2K21 (Viamechanics)) for wet cleaning.
[0501] Subsequently, a seed layer was formed by electroless plating to attempt to form a conductor layer with a wiring pattern of L / S = 1 / 1 μm. However, the arithmetic mean roughness (Ra) of the insulating material layer surface was high, and therefore, due to the inhomogeneity of electroless plating, wiring formation was lacking and could not be formed.
[0502] [Comparative Example 4]
[0503] In Example 1, the following steps were changed: (2) lamination of the thermosetting resin sheet, (3) thermosetting of the thermosetting material layer, (4) lamination of the photosensitive resin sheet A, (5) patterning of the photosensitive material layer, and (6) formation of the through-hole. Except for the above, the substrate B was fabricated and evaluated in the same manner as in Example 1.
[0504] The protective film of photosensitive resin film A is peeled off, and the photosensitive material layer is laminated to one side of the silicon wafer using an intermittent vacuum pressure laminator (NIKKO MATERIALS, two-stage laminator, CVP700), with the photosensitive material layer in contact with the silicon wafer. The lamination is performed as follows: depressurization for 30 seconds to bring the pressure below 13 hPa, followed by pressing at 130°C and 0.74 MPa for 45 seconds. Then, thermal pressurization is performed at 120°C and 0.5 MPa for 75 seconds.
[0505] After laminating photosensitive resin film A, substrate A was baked at 80°C for 30 seconds and exposed for 1800 msec using a Ushio UX-2240 electric motor. After exposure, substrate A was baked at 75°C for 180 seconds and then developed using a 2.38% TMAH solution under paddle conditions of 30 seconds × 2 cycles. The developed pattern was then descaled using a plasma apparatus manufactured by SAMCO (O2 flow rate: 50 sccm, RF power: 500 W, process pressure: 12 Pa, processing time: 1 minute). Subsequently, it was treated with 5000 mJ / cm². 2 After exposure and baking, the material is post-cured to obtain an insulating material layer with through holes.
[0506] [Comparative Example 5]
[0507] In Comparative Example 1, thermosetting resin sheet 2 was replaced with thermosetting resin sheet 1. Except for the above, the same procedures were followed as in Comparative Example 1 for the fabrication and evaluation of substrate B.
[0508] In Comparative Example 5, a Cu mask pattern was used to attempt to form vias and a conductor layer. However, due to the high surface roughness of the cured thermosetting material, it was difficult to etch when forming the plating seed layer. Therefore, it was impossible to form a conductor layer with a wiring pattern of L / S = 1 / 1 μm.
[0509] [Comparative Example 6]
[0510] In Comparative Example 2, thermosetting resin sheet 2 was replaced with thermosetting resin sheet 1. Except for the above, the same procedures were followed as in Comparative Example 2 for the fabrication and evaluation of substrate B.
[0511] [Comparative Example 7]
[0512] In Comparative Example 3, thermosetting resin sheet 2 was replaced with thermosetting resin sheet 1. Except for the above, the same procedures as in Comparative Example 3 were followed for the fabrication and evaluation of substrate B. In Comparative Example 7, a plating seed layer was formed using an electroless plating process to attempt to form a conductor layer with a wiring pattern having an L / S = 1 / 1 μm. However, the arithmetic mean roughness (Ra) of the insulating material layer surface was high, and therefore, due to the inhomogeneity of the electroless plating, wiring formation was lacking, and formation was impossible.
[0513] [Table 2]
[0514]
[0515] [Table 3]
[0516]
[0517] <Preparation of solidified samples>
[0518] Photosensitive materials 1-5 were coated onto a release PET film with a film thickness of 140 μm using a scraper. The solution on the release PET film was heated at 80°C for 20 minutes using a heater to form a photosensitive resin sheet with a photosensitive material layer. The photosensitive material layer was peeled off from the release PET film and adhered to a metal frame using heat-resistant tape. Curing was then performed at 200°C for 120 minutes (230°C for 120 minutes only when using photosensitive material 2), producing a cured sample. For photosensitive material 1, at 3000 mJ / cm²... 2 After exposure under certain conditions, additional thermosetting is performed.
[0519] Using a die-coating machine, thermosetting materials 1 to 4 were uniformly coated onto a polyimide film with a dried thermosetting material layer thickness of 20 μm. The film was then dried at 70°C to 95°C for 2 minutes to produce a resin sheet with a thermosetting material layer on the polyimide film. Next, after curing at 200°C for 120 minutes, the polyimide film was peeled off to obtain a cured sample.
[0520] <Determination of Glass Transition Temperature and Coefficient of Linear Thermal Expansion>
[0521] The cured sample obtained above was cut into pieces 20 mm long and 6 mm wide to obtain the evaluation cured sample. For this evaluation cured sample, a thermomechanical analysis (TMA) apparatus (Rigaku Corporation) was used to obtain the first TMA curve using the tensile loading method, heating from 25°C to 250°C at a rate of 5°C / min. Subsequently, the same measurement was performed on the same evaluation cured sample, obtaining a second TMA curve using the tensile loading method, heating from 25°C to 250°C at a rate of 5°C / min. The glass transition temperature Tg (°C) and the coefficient of linear thermal expansion (CTE: (ppm / °C)) were determined based on the second TMA curve.
[0522] <Determination of dielectric loss tangent and dielectric constant>
[0523] The cured sample obtained above was cut into test pieces with an actual width of 2 mm and a length of 80 mm. For these test pieces, using the cavity resonance method with an Agilent Technologies HP8362B instrument, measurements were taken on three test pieces at a measurement frequency of 5.8 GHz and a measurement temperature of 23 °C. The average value was used as the dielectric loss tangent and dielectric constant.
[0524] Evaluation of elastic modulus and elongation at break
[0525] For thermosetting materials, the cured sample was cut into dumbbell-shaped pieces (No. 1) to obtain test pieces. For photosensitive materials, dumbbell-shaped pieces (No. 1) were exposed and developed. The photosensitive material layer was then adhered to a metal frame using heat-resistant tape, followed by curing at 200°C for 120 minutes (230°C for 120 minutes only when using photosensitive resin sheets obtained from photosensitive material 2), to create test pieces. For photosensitive material 1, at 3000 mJ / cm 2 After exposure under specific conditions, additional thermosetting was performed. Tensile strength was measured using an ORIENTEC RTC-1250A tensile testing machine at 23°C, determining the elastic modulus and elongation at break. Measurements were conducted according to JIS K7127. Ten measurements were performed (n=10), and the average of the three points with the highest elongation was calculated.
[0526] [Table 4]
[0527] (Table 4)
[0528]
[0529] Explanation of reference numerals in the attached figures
[0530] 10 substrate
[0531] 11 Insulation Material Layer
[0532] 12 Inner layer circuit board
[0533] 20 Photosensitive material layers
[0534] 21. Plasma Mask (Permanent Film)
[0535] 22 First photosensitive material layer
[0536] 23 Second photosensitive material layer
[0537] 24 First Plasma Mask (Permanent Membrane)
[0538] 25 Second Plasma Mask
[0539] 211 Opening
[0540] 212 Opening
[0541] 30 through hole
[0542] 31. Trench
[0543] 40 Patterned Conductor Layer
[0544] 41. Seed layer plating
[0545] 42 Electrolytic plating coating
Claims
1. A method for manufacturing a wiring board, comprising: (1) preparing a substrate having a conductor circuit and an insulating material layer formed of a cured product of a thermosetting material on the conductor circuit, and performing any one or both of coating and pasting a photosensitive material on the surface of the insulating material layer to form a photosensitive material layer; (2) exposing and developing the photosensitive material layer to form a plasma mask having openings; (3) irradiating the insulating material layer with plasma through the plasma mask to form either or both of a through hole and a trench in the insulating material layer located at the openings of the plasma mask, and reducing the film thickness of the plasma mask; and (4) forming a conductor layer on the surface of the plasma mask with reduced film thickness and either or both of the through hole and the trench.
2. The method for manufacturing a wiring board according to claim 1, wherein, Step (4) includes: (4-1) forming a plating seed layer on the surface of the plasma mask with reduced film thickness and either or both of the through hole and the trench; and (4-2) performing plating on the plating seed layer to form a conductor layer.
3. The method for manufacturing a wiring board according to claim 1, wherein, The conductor layer includes either or both of a conductor wiring formed at a position other than the openings of the plasma mask and a conductor hole layer formed at the openings of the plasma mask.
4. The method for manufacturing a wiring board according to claim 2, wherein the plating seed layer is formed by a dry plating method.
5. The method for manufacturing a wiring board according to claim 1, wherein, The opening diameter of the through hole or the trench is 20 μm or less.
6. The method for manufacturing a wiring board according to claim 1, wherein, The thickness of the plasma mask with reduced film thickness after step (3) is 0.1 μm or more and 20 μm or less.
7. The method for manufacturing a wiring board according to claim 1, wherein, The wiring pitch of the conductor circuit is 0.2 μm or more and 10 μm or less.
8. The method for manufacturing a wiring board according to claim 1, wherein, The arithmetic mean roughness (Ra) of the surface of the plasma mask with reduced film thickness after step (3) is 100 nm or less.
9. The method for manufacturing a wiring board according to claim 1, wherein, The roughness (Sa) of the wall surface of the through hole or the trench is 400 nm or less.
10. The method for manufacturing a wiring board according to claim 1, wherein, The ratio (Ra / Sa) of the arithmetic mean roughness (Ra) of the surface of the plasma mask with reduced film thickness after step (3) to the roughness (Sa) of the wall surface of the through hole or the trench is 3 or less.
11. The method for manufacturing a wiring board according to claim 1, wherein, The thickness of the photosensitive material layer is 1 μm or more and 100 μm or less.
12. The method for manufacturing a wiring board according to claim 1, wherein, When the thickness of the plasma mask before plasma irradiation is set to 1, the thickness of the plasma mask with reduced film thickness after step (3) is 0.7 or less.
13. The method for manufacturing a wiring board according to claim 1, wherein, [[ID=^18]]The absolute value of the difference between the linear thermal expansion coefficient of the cured product of the photosensitive material and the linear thermal expansion coefficient of the cured product of the insulating material in the range of 25 °C to 150 °C is 60 ppm / °C or less.
14. The method for manufacturing a wiring board according to claim 1, wherein, When the thickness of the plasma mask with reduced film thickness after step (2) is set to T1 and the thickness of the insulating material layer after step (2) is set to T2, the relationship T1>T2 is satisfied.
15. The method for manufacturing a wiring board according to claim 1, wherein, When the thickness of the plasma mask with reduced film thickness after step (3) is set to T3 and the thickness of the insulating material layer after step (3) is set to T4, the relationship T3<T4 is satisfied.
16. The method for manufacturing a wiring board according to claim 1, wherein, The absolute value of the difference between the glass transition temperature of the photosensitive material contained in the plasma mask and the glass transition temperature of the thermosetting material is 100 °C or less.
17. The method for manufacturing a wiring board according to claim 1, wherein, The hole taper angle of the through hole or the trench is 65 degrees or more and 90 degrees or less.
18. The method for manufacturing a wiring board according to claim 1, wherein, The hole expansion rate is 105% or more and 150% or less.
19. The method for manufacturing a wiring board according to claim 1, wherein, The relative permittivity of cured photosensitive materials and cured thermosetting materials is both below 3.
5.
20. The method for manufacturing a wiring board according to claim 1, wherein, The elongation at break of cured photosensitive materials is greater than 10%, which is greater than that of cured thermosetting materials.
21. The method for manufacturing a wiring board according to claim 1, wherein, The etching rate in process (3) is above 100 nm / min.
22. The method for manufacturing a wiring board according to claim 1, wherein, The line width of the conductor layer / the spacing between conductor layers (L / S) is less than 5μm / 5μm.
23. The method for manufacturing a wiring board according to claim 1, wherein the wiring board substrate comprises three or more conductor layers.
24. The method for manufacturing a wiring board according to claim 1, wherein, The area of the wiring board is 2500mm². 2 above.
25. The method for manufacturing a wiring board according to claim 1, wherein, The photosensitive material used in step (1) contains at least one of resins and epoxy resins that can be developed using a developer.
26. The method for manufacturing a wiring board according to claim 25, wherein, The resin capable of being developed using a developer contains one or more of the following: alkali-soluble resins with phenolic hydroxyl groups within the molecule, polyimide precursors, polybenzoxazole precursor resins, and acrylic resins.
27. The method for manufacturing a wiring board according to claim 1, wherein, The photosensitive material used in process (1) contains inorganic filler material, and the content of inorganic filler material in the photosensitive material is less than 10% by mass relative to 100% by mass of the non-volatile components of the photosensitive material.
28. The method for manufacturing a wiring board according to claim 1, wherein, Thermosetting materials contain inorganic fillers, and the content of inorganic fillers in thermosetting materials is more than 20% by mass relative to 100% of the non-volatile components of thermosetting materials.
29. The method for manufacturing a wiring board according to claim 28, wherein, The content of inorganic filler material is between 35% and 90% of the non-volatile components of thermosetting material per 100% mass.
30. The method for manufacturing a wiring board according to claim 1, wherein, The photosensitive material used in process (1) contains inorganic filler material, and the average particle size of the inorganic filler material in the photosensitive material is less than 0.2 μm. The thermosetting material contains inorganic filler material, and the average particle size of the inorganic filler material is greater than 0.01 μm.
31. The method for manufacturing a wiring board according to claim 1, wherein, The linear thermal expansion coefficient of the plasma mask after the reduction film is combined with the insulating material layer after process (3) is less than 100ppm / ℃ in the range of 25℃ to 150℃.
32. The method for manufacturing a wiring board according to claim 1, wherein, The photosensitive material used in process (1) is solvent-developable negative photosensitive polyimide resin.
33. The method for manufacturing a wiring board according to claim 1, wherein, Process (1) includes at least one of the following: Coating with liquid photosensitive materials, and A photosensitive material layer comprising a support and a photosensitive material layer formed of a photosensitive material disposed on the support.
34. The method for manufacturing a wiring board according to claim 1, wherein, The total thickness of the insulating material layer and the subtractive plasma mask is less than 15 μm.
35. The method for manufacturing a wiring board according to claim 1, comprising: The process of attaching a thermosetting resin sheet containing a support and a thermosetting material layer formed of thermosetting material disposed on the support to a conductor circuit, and curing the thermosetting material layer to form an insulating material layer.
36. A method for manufacturing a wiring board, comprising: (A) A process of preparing a substrate having a conductor circuit and an insulating material layer formed on the conductor circuit by a cured thermosetting material, and applying or both of coating and pasting a first photosensitive material to the surface of the insulating material layer to form a first photosensitive material layer. (B) The process of exposing and developing the first photosensitive material layer to form a first plasma mask with an opening; (C) A process of irradiating an insulating material layer with plasma through a first plasma mask, forming either or both of a via and a trench in the insulating material layer at the opening of the plasma mask, and performing a reduction film process on the plasma mask. (D) A process of forming a second photosensitive material layer by coating and pasting a second photosensitive material in a manner that covers the surface and opening of a first plasma mask. (E) The process of exposing and developing the second photosensitive material layer to form a second plasma mask with an opening; (F) The process of irradiating a first plasma mask and an insulating material layer with plasma through a second plasma mask to form either or both of a through hole and a trench in the insulating material layer; (G) The process of forming a conductor layer on the surface of the first plasma mask and either or both of the vias and trenches; and (H) The process of grinding the surface of the conductor layer.
37. A wiring board manufactured by the method of manufacturing a wiring board according to any one of claims 1 to 36.
38. The wiring board according to claim 37, which is formed in the order of conductor circuit, insulating material layer, plasma mask and conductor layer, and has through holes.
39. The wiring board according to claim 38, comprising two or more conductor circuits, an insulating material layer, a plasma mask, a conductor layer, and a through-hole.
40. A semiconductor device comprising a wiring board manufactured by the method of manufacturing a wiring board according to any one of claims 1 to 36.
41. The semiconductor device of claim 40, having a fan-out configuration.
42. The semiconductor device of claim 40, having a chiplet structure.
43. A semiconductor device having a semiconductor chip on a wiring board manufactured by any one of claims 1 to 36.
44. The semiconductor device of claim 40, wherein, Semiconductor chips are a hybrid system of at least logic chips and memory chips.
Citation Information
Patent Citations
Photosensitive film with support and method for producing the same
JP2018169547A
Photosensitive resin composition and method for producing cured relief pattern
JP2018169627A
Resin composition
JP2020015859A
Resin composition, photosensitive film, photosensitive film with support, printed wiring board and semiconductor device
JP2020052288A
Resin composition
JP2020075977A